Compositions and methods
By forming a mixed platform catalyst composition of hydroxyl and Lewis acid sites at an appropriate distance on the catalyst surface, the problems of high pressure, high temperature and long reaction time during CO2 fixation in the prior art are solved, and efficient CO2 insertion and polycarbonate are achieved The production of ester-polyether copolymers improves catalytic activity and recyclability.
Patent Information
- Application Number
- CN202411235772.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-17
- Filing Date
- 2020-12-16
- Publication Date
- 2024-12-13
AI Technical Summary
During the fixation and utilization of CO2, existing catalysts have problems of high pressure, high temperature and long reaction times, and it is difficult to effectively insert CO2 into the polymer structure, resulting in mostly polyethers rather than polycarbonate, and lack of recyclable and Highly efficient heterogeneous catalyst.
A mixed platform catalyst composition was developed to form appropriate distance hydroxyl and Lewis acid sites on the catalyst surface through the use of regulators, promote the reaction of CO2 with monomer molecules, form polymers, and control microcrystals through specific synthetic methods Size and particle morphology.
Catalyzed the insertion of CO2 under mild conditions, resulting in a high content of carbonate bonded polycarbonate-polyether copolymer, which shortens the reaction time and energy consumption, and improves the activity and recyclability of the catalyst.
Smart Images

Figure BDA0005027689130000431 
Figure BDA0005027689130000471 
Figure BDA0005027689130000481
Abstract
Description
[0001] This application is a divisional application of an application filed on December 16, 2020, with application number 202080088537.1, and invention name “Compositions and Methods”. Field of the Invention
[0002] The present invention relates to a composition useful as a catalyst. The present invention also relates to a method for producing the composition and the use of the composition for catalytic reactions, particularly but not exclusively to the use of CO 2 Reactions incorporated into molecular structures. Background of the Invention
[0003] As environmental concerns about greenhouse gas emissions increase, large amounts of carbon dioxide (CO 2 ) remains a key area of research. 2 The method used is epoxide and CO 2 Catalytic ring-opening copolymerization (ROCOP) to form poly(alkylene) carbonates.
[0004] The use of high-energy substrates such as epoxides provides a sustainable alternative to the conventional ring-opening polymerization (ROP) of cyclic carbonate monomers or the toxic polycondensation with trans-diols and phosgene to afford aliphatic polycarbonates while consuming CO2. 2 The formation of poly(propylene) carbonate (PPC) can produce a polymer in which 43% of the polymer weight is attributed to CO 2 . Low molecular weight (M) with hydroxyl end groups n ) PPC or 'polycarbonate polyol' is used as a sustainable alternative to polyether polyols in the manufacture of polyurethane, a material found widely in flexible or rigid foams, sealants, coatings and elastomers. Since the synthesis of polyurethane relies on the homopolymerization of petrochemically derived epoxides, the ROCOP pathway uses renewable CO 2 Replacing some of these epoxides is a step toward reduced reliance on petrochemical feedstocks.
[0005] Most commonly, ROCOP is catalyzed by homogeneous metal complexes with Lewis acidity, of which chromium (III) or cobalt (III) salts and Zn-β-diiminate complexes are the most active. Unfortunately, removal of these catalysts from the polymer product is not easy, and there are few viable examples of heterogeneous, recyclable catalysts that can perform this transformation with significant catalytic turnover and without the need for nucleophilic cocatalysts or solvents.
[0006] Examples of recyclable, easily separable heterogeneous systems with high polycarbonate selectivity have been limited to double metal cyanide (DMC) complexes and zinc glutarates (ZnGAs). For example, US4943677, US4981948 and US5026676 all describe the synthesis of zinc glutarate catalysts for CO 2 and epoxides to form poly(alkylene carbonates).
[0007] Similarly, Zhu, Q. et al. Polym. Int. 2002, 51(10), 1079-1085; Eberhardt, R. et al. Macromol. Chem. Phys. 2004, 205(1), 42-47; and Marbach, J. et al. Catal. Sci. Technol. 2017, 7(13), 2897-2905; Ree, M. et al. J. Polym. Sci. Part Polym. Chem. 1999, 37(12), 1863-1876; and Ree, M. et al. Catal. Today 2006, 115(1), 134-145 all describe the synthesis of zinc glutarate catalysts for CO 2 and epoxides to form poly(alkylene carbonates).
[0008] Zinc glutarate catalysts have a number of disadvantages: they require high pressure (typically 40 to 50 atmospheres of CO 2 ), higher temperature (typically 60°C-100°C), higher metal loading (typically 30 wt% Zn), long reaction time (typically 40 hours), and non-negligible reaction parameters are required to obtain satisfactory polymer yields.
[0009] US4500704, US4826953 and CA1262597A describe the synthesis of double metal cyanide catalysts for CO 2 and epoxides to form poly(alkylene carbonates).
[0010] Similarly, Meng, Q. et al. J. CO2 Util. 2016, 16, 86-96 describe the synthesis of a composite double metal cyanide / zinc glutarate catalyst for CO 2and epoxides to form poly(alkylene carbonates). The reaction described in this document uses NP-40, a nonionic surfactant that is said to inhibit the particle growth of zinc glutarate. However, the document does not describe the effect of the compound on the crystallite size of the catalyst thus produced. In addition, double metal cyanide has the property of converting CO 2 Very poor ability to insert into polymers (typically 10%-56% CO based on literature) 2 Insert). Therefore, when used to catalyze the copolymerization reaction, most of the products tend to be polyethers rather than polycarbonates. In addition, the polymers produced according to the process described in the article are high molecular weight polymers, all having a number average molecular weight (M) exceeding 10 kDa. n ).
[0011] Metal-organic framework (MOF) complexes are generally known in the art. Typically, MOFs include structures of metal ions bound together via multivalent linker groups coordinated to the metal ions. An example of a MOF is a structure known as MIL-100, in which trivalent metal ions are linked together via benzene-1,3,5-tricarboxylate (trimesate) linker groups. The metal ions may be Cr 3+ , Fe 3+ 、Al 3+ 、V 3+ Sc 3+ or In 3+ .
[0012] MOFs have become versatile materials in many fields due to their exceptional porosity and the ease with which their structural components can be modified to provide customized materials. 2 Adsorption capacity, many MOFs have been explored as potential catalysts for ROCOP reactions: Cabello, CP, et al. Cryst. Eng. Comm 2015, 17, 430-437 and Cabello, CP et al., Microporous Mesoporous Mater. 2014, 190, 234-239. However, to date, MOFs have only been shown to form thermodynamically favorable cyclic carbonate products, usually with the help of tertiary ammonium halide co-catalysts, wherein no examples of copolymerization have occurred so far. The activity of these MOFs has been attributed to the regular arrangement (regular array) of Lewis acid sites (hereinafter described as "B-sites") within the framework of the composition. Typically, epoxides are combined with B-sites. Nucleophilic co-catalysts (usually tertiary ammonium halides) ring open epoxides, and epoxides remain combined with B-sites via metal-alkoxy bonds. Then, CO 2Insertion into the metal-alkoxy bond occurs and chain growth continues at the B-site.
[0013] One such example of a MOF is MIL-100(Sc), a highly porous, trimesate-based MOF formed from corner-sharing supertetrahedrons with triangular prismatic metal oxide trimers at the vertices. Many publications describe MIL-100(Sc), its synthesis and characterization, and the reactions that this framework can facilitate.
[0014] For example, JPS Mowat et al. Microporous and Mesoporous Materials 2011, 142, 322-333 describe the synthesis, characterization and adsorption properties of microporous scandium carboxylates with rigid and flexible frameworks. In addition, Mitchell et al. Catal. Sci. Technol., 2013, 3, 606-617 describe MIL-100 (Sc) and its use as a Lewis acid catalyst for CC bond formation and CQN bond formation (ene reaction of activated carbonyl). However, neither of these two publications explicitly describes that the distance between the sites defined herein as A-site and B-site is close enough to enable the composition to interact with the monomer (especially the monomer and CO). 2 ) in order to be able to catalyze polymerization reactions, especially those in which CO 2 The polymerization reaction is incorporated into the structure of the polymer. Furthermore, there is no evidence in either publication (eg, from SEM images or TEM images) that the method achieves the crystallite control or particle control achieved using the method of the present invention.
[0015] Mitchell et al., Chem. Eur. J. 2014, 20, 17185-17197 describe mixed metal MIL-100 (Sc, M) (wherein M = Al, Cr, Fe) and its use for Lewis acid catalysis and tandem CC bond formation and alcohol oxidation. Giovine et al., Chem. Eur. J. 2017, 23, 9525-9534 describe the analysis of MIL-100 (Sc) by solid-state NMR spectroscopy. Li et al., Chinese Journal of Inorganic Chemistry, 2011 27, 5, 951-956 describe metal-organic frameworks of scandium carboxylates having MIL-100 structures and MIL-101 structures.
[0016] However, none of these publications describe compositions in which the bulk material includes metal ions bonded to each other via linker groups, but has a surface structure in which the site to which the hydroxyl group is bound (also described herein as the "A-site") is present in close enough proximity to the Lewis acidic B-site to enable both the A-site and the B-site to maximize catalytic activity. There is no teaching in the art of compositions that can be used as hybrid platform catalysts (as described and claimed herein) having these two sites at a distance from each other so that they can both play a role in catalysis; nor is there any teaching of the use of such compositions in methods of forming polymers as described and claimed herein, in which CO 2 are incorporated into the structure of the polymer.
[0017] J. Liang et al. Coordination Chemistry Reviews, 2019, 378, 32-65 provided CO 2 A review of the entrapment and immobilization of cyclic carbonates and their catalysis by metal-organic frameworks and porous organic polymers. However, this publication also does not explicitly describe that the distance between the sites, defined herein as the A-site and the B-site, is close enough to allow the composition to interact with the monomer (particularly the monomer and CO 2 ) in order to be able to catalyze polymerization reactions, especially those in which CO 2 A polymerization reaction is incorporated into the structure of a polymer. Furthermore, there is no evidence in this publication (eg, from SEM images or TEM images) that the method achieves the crystallite control or particle control achieved using the method of the present invention. SUMMARY OF THE INVENTION
[0018] In one aspect of the present invention, there is provided a composition comprising:
[0019] bulk material; and
[0020] at least one surface;
[0021] The bulk material includes ions of metal M bonded to each other via linker groups;
[0022] The surface comprises ions of metal M' bonded to each other via linker groups;
[0023] Metal M and metal M' are the same or different;
[0024] The surface comprises at least one first site A and at least one second different site B;
[0025] Site A has a hydroxyl group bonded thereto, said site A optionally being capable of bonding to a CO 2 interaction;
[0026] Site B is capable of binding CO 2 Lewis acidic sites of the molecule;
[0027] The distance d between site A and site B is such that the monomer molecule Y and the bound CO 2 can react together on the surface to form a polymer where CO 2 are incorporated into the structure of the polymer.
[0028] In another aspect, a composition is provided, comprising:
[0029] The bulk material; and
[0030] at least one surface;
[0031] The bulk material includes ions of metal M bonded to each other via linker groups;
[0032] The surface comprises ions of metal M' bonded to each other via linker groups;
[0033] Metal M and metal M' are the same or different;
[0034] The surface comprises at least one first site A and at least one second different site B;
[0035] Site A has a hydroxyl group bonded thereto, said site A being capable of interacting with a monomer molecule;
[0036] Site B is a Lewis acidic site, and the site B can interact with a monomer molecule;
[0037] The distance d between site A and site B allows monomer molecules to polymerize on the surface to form a polymer.
[0038] In another aspect, a composition is provided, comprising:
[0039] The bulk material; and
[0040] at least one surface;
[0041] The bulk material includes ions of metal M bonded to each other via linker groups;
[0042] The surface comprises ions of metal M' bonded to each other via linker groups;
[0043] Metal M and metal M' are the same or different;
[0044] The surface comprises at least one first site A and at least one second different site B;
[0045] Site A has a hydroxyl group bonded thereto, said site A being capable of interacting with a monomer molecule;
[0046] Site B is a Lewis acidic site, and the site B can interact with a monomer molecule;
[0047] The composition is obtainable by reacting a source of metal ions M and a source of metal ions M' with a source of linker groups and a source of hydroxyl groups in the presence of a modulator under conditions such that the surface of the composition has a first site A to which hydroxyl groups are attached and a second site B that is Lewis acidic.
[0048] In one embodiment, the composition is a microcrystalline composition.
[0049] In another aspect, a microcrystalline composition is provided, comprising:
[0050] The bulk material; and
[0051] at least one surface;
[0052] The bulk material includes ions of metal M bonded to each other via linker groups;
[0053] The surface comprises ions of metal M' bonded to each other via linker groups;
[0054] Metal M and metal M' are the same or different;
[0055] The surface comprises at least one first site A and at least one second different site B;
[0056] Site A has a hydroxyl group bonded thereto, said site A being capable of interacting with a monomer molecule;
[0057] Site B is a Lewis acidic site, which is capable of interacting with a monomer molecule.
[0058] In another aspect, a composition is provided, comprising:
[0059] The bulk material; and
[0060] at least one surface;
[0061] The bulk material includes ions of metal M bonded to each other via linker groups;
[0062] The surface comprises ions of metal M' bonded to each other via linker groups;
[0063] Metal M and metal M' are the same or different;
[0064] The surface comprises at least one first site A and at least one second different site B;
[0065] Site A has a hydroxyl group bonded thereto;
[0066] Site B is a Lewis acidic site;
[0067] The distance d between site A and site B allows monomer molecules to polymerize on the surface to form a polymer.
[0068] In another aspect, a composition is provided, comprising:
[0069] The bulk material; and
[0070] at least one surface;
[0071] The bulk material includes ions of metal M bonded to each other via linker groups;
[0072] The surface comprises ions of metal M' bonded to each other via linker groups;
[0073] Metal M and metal M' are the same or different;
[0074] The surface comprises at least one first site A and at least one second different site B;
[0075] Site A has a hydroxyl group bonded thereto;
[0076] Site B is a Lewis acidic site;
[0077] The composition is obtainable by reacting a source of metal ions M and a source of metal ions M' with a source of linker groups and a source of hydroxyl groups in the presence of a modulator under conditions such that the surface of the composition has a first site A to which hydroxyl groups are attached and a second site B that is Lewis acidic.
[0078] In another aspect, a microcrystalline composition is provided, comprising:
[0079] The bulk material; and
[0080] at least one surface;
[0081] The bulk material includes ions of metal M bonded to each other via linker groups;
[0082] The surface comprises ions of metal M' bonded to each other via linker groups;
[0083] Metal M and metal M' are the same or different;
[0084] The surface comprises at least one first site A and at least one second different site B;
[0085] Site A has a hydroxyl group bonded thereto; and
[0086] Site B is a Lewis acidic site.
[0087] In another aspect of the present invention, a method for forming a composition of the present invention is provided, the method comprising reacting a source of metal ions M and a source of metal ions M' with a source of linker groups and a source of hydroxyl groups in the presence of a modulator; and subjecting the composition to conditions such that the surface of the composition has a first site A to which a hydroxyl group is attached and a second site B that is Lewis acidic.
[0088] In another aspect of the present invention, a method for forming the composition of the present invention is provided, the method comprising reacting a source of metal ions M and a source of metal ions M' with a source of linker groups and a source of hydroxyl groups; and subjecting the composition to conditions such that the surface of the composition has a first site A to which a hydroxyl group is attached and a second site B that is Lewis acidic.
[0089] In one embodiment, the stoichiometric ratio of the modulator to the source of linker groups is between 50:1 and 1:5.
[0090] In one embodiment, the stoichiometric ratio of the modulator to the source of linker groups is between 20:1 and 1:2.
[0091] In one embodiment, the stoichiometric ratio of the metal ion source to the modifier is between 1:0.1 and 1:500.
[0092] In one embodiment, the modulator is selected from the group consisting of trifluoroacetic acid, trichloroacetic acid, acetic acid, and benzoic acid.
[0093] In one embodiment, the method comprises the following sequential steps (a) and (b):
[0094] (a) mixing the metal ion source with the conditioning agent; and
[0095] (b) adding the linker to the mixture formed in step (a).
[0096] In one embodiment, the method is carried out in a solvent and the stoichiometric ratio of the metal ion source to the solvent is between 1:10 and 1:200.
[0097] In one embodiment, following reaction of said metal ion source and said linker source, the reaction mixture is cooled to a temperature of less than 10°C.
[0098] In a further aspect of the invention there is provided the use of a composition of the invention as a catalyst, particularly but not exclusively as a catalyst for catalysing polymerisation reactions.
[0099] In a further aspect of the invention there is provided a method of forming a polymer comprising polymerising a monomer in the presence of a composition of the invention.
[0100] In another aspect of the present invention, a method of forming a polymer is provided, wherein CO 2 is incorporated into the structure of the polymer, the method comprising 2 and the composition of the present invention.
[0101] In a further aspect of the invention, there is provided a method of forming a polymer, the method comprising polymerizing a monomer in the presence of a composition comprising:
[0102] The bulk material; and
[0103] at least one surface;
[0104] The bulk material includes ions of metal M bonded to each other via linker groups;
[0105] The surface comprises ions of metal M' bonded to each other via linker groups;
[0106] Metal M and metal M' are the same or different;
[0107] The surface comprises at least one first site A and at least one second different site B;
[0108] Site A has a hydroxyl group bonded thereto, said site A being capable of interacting with a monomer molecule;
[0109] Site B is a Lewis acid site that can interact with the monomer molecule;
[0110] The distance d between site A and site B allows monomer molecules to polymerize on the surface to form a polymer.
[0111] In a further aspect of the invention, there is provided a method of forming a polymer, the method comprising polymerizing a monomer in the presence of a microcrystalline composition comprising:
[0112] The bulk material; and
[0113] at least one surface;
[0114] The bulk material includes ions of metal M bonded to each other via linker groups;
[0115] The surface comprises ions of metal M' bonded to each other via linker groups;
[0116] Metal M and metal M' are the same or different;
[0117] The surface comprises at least one first site A and at least one second different site B;
[0118] Site A has a hydroxyl group bonded thereto, said site A being capable of interacting with a monomer molecule; and
[0119] Site B is a Lewis acid site capable of interacting with a monomer molecule.
[0120] In a further aspect of the invention, there is provided a method of forming a polymer, the method comprising polymerizing a monomer in the presence of a composition comprising:
[0121] The bulk material; and
[0122] at least one surface;
[0123] The bulk material includes ions of metal M bonded to each other via linker groups;
[0124] The surface comprises ions of metal M' bonded to each other via linker groups;
[0125] Metal M and metal M' are the same or different;
[0126] The surface comprises at least one first site A and at least one second different site B;
[0127] Site A has a hydroxyl group bonded thereto, said site A being capable of interacting with a monomer molecule;
[0128] Site B is a Lewis acidic site, and the site B can interact with a monomer molecule;
[0129] The composition is obtainable by reacting a source of metal ions M and a source of metal ions M' with a source of linker groups and a source of hydroxyl groups in the presence of a modulator under conditions such that the surface of the composition has a first site A to which hydroxyl groups are attached and a second site B that is Lewis acidic.
[0130] In another aspect of the present invention, a method of forming a polymer is provided, wherein CO 2 is incorporated into the structure of the polymer, the method comprising reacting the following in the presence of the composition:
[0131] (a) a molecule Y which is a monomer capable of polymerizing to form a polymer, wherein CO 2 is incorporated into the structure of the polymer; and
[0132] (b)CO 2 ;
[0133] The composition includes a bulk material; and
[0134] at least one surface;
[0135] The bulk material includes ions of metal M bonded to each other via linker groups;
[0136] The surface comprises ions of metal M' bonded to each other via linker groups;
[0137] Metal M and metal M' are the same or different;
[0138] The surface comprises at least one first site A and at least one second different site B;
[0139] Site A has a hydroxyl group bonded thereto, said site A optionally being capable of bonding to a CO 2 interaction;
[0140] Site B is capable of binding CO 2 The molecule makes the bound CO 2 The molecule can react with the monomer molecule Y Lewis acid site;
[0141] The distance d between site A and site B is such that the molecule Y and the bound CO 2 can react together on the surface to form a polymer.
[0142] In another aspect of the present invention, a method of forming a polymer is provided, wherein CO 2 is incorporated into the structure of the polymer, the method comprising reacting the following in the presence of a microcrystalline composition:
[0143] (a) a molecule Y which is a monomer capable of polymerizing to form a polymer, wherein CO 2 is incorporated into the structure of the polymer; and
[0144] (b)CO 2 ;
[0145] The microcrystalline composition includes a bulk material; and
[0146] at least one surface;
[0147] The bulk material includes ions of metal M bonded to each other via linker groups;
[0148] The surface comprises ions of metal M' bonded to each other via linker groups;
[0149] Metal M and metal M' are the same or different;
[0150] The surface comprises at least one first site A and at least one second different site B;
[0151] Site A has a hydroxyl group bonded thereto, said site A optionally being capable of bonding to a CO 2 interaction;
[0152] Site B is capable of binding CO 2 The molecule makes the bound CO 2 The Lewis acid site of the molecule can react with the monomer molecule Y; so that the molecule Y and the bound CO 2 react together on the surface to form a polymer.
[0153] In another aspect of the present invention, a method of forming a polymer is provided, wherein CO 2 is incorporated into the structure of the polymer, the method comprising reacting the following in the presence of the composition:
[0154] (a) a molecule Y which is a monomer capable of polymerizing to form a polymer, wherein CO 2 is incorporated into the structure of the polymer; and
[0155] (b)CO 2 ;
[0156] The composition includes a bulk material; and
[0157] at least one surface;
[0158] The bulk material includes ions of metal M bonded to each other via linker groups;
[0159] The surface comprises ions of metal M' bonded to each other via linker groups;
[0160] Metal M and metal M' are the same or different;
[0161] The surface comprises at least one first site A and at least one second different site B;
[0162] Site A has a hydroxyl group bonded thereto, said site A optionally being capable of bonding to a CO 2 interaction;
[0163] Site B is capable of binding CO 2 The molecule makes the bound CO 2 The Lewis acid site of the molecule can react with the monomer molecule Y; so that the molecule Y and the bound CO2 react together on the surface to form a polymer;
[0164] The composition is obtainable by reacting a source of metal ions M and a source of metal ions M' with a source of linker groups and a source of hydroxyl groups in the presence of a modulator under conditions such that the surface of the composition has a first site A to which hydroxyl groups are attached and a second site B that is Lewis acidic.
[0165] In one embodiment, the metal ion M and the metal ion M' are selected from Sc 3+ Cr 3+ 、Al 3+ and Fe 3+ .
[0166] In one embodiment, the linker group has the structure T(R) x (R') y (H) z ,in:
[0167] T is a multivalent organic moiety;
[0168] R is a functional group capable of coordinating with the metal ion M and the metal ion M';
[0169] R' is a functional group that cannot coordinate with the metal ion M and the metal ion M', and the functional group is not H;
[0170] x is 2 to 6;
[0171] y is 0 to 4; and
[0172] z is a number sufficient to occupy the remaining valencies on T.
[0173] In one embodiment, T is a cycloalkyl ring, a heterocycloalkyl ring, an aryl ring, or a heteroaryl ring.
[0174] In one embodiment, R is -CO 2 H.
[0175] In one embodiment, R' is selected from -SO 3 H.C 1-6 Alkyl and halogen.
[0176] In one embodiment, the distance d is between 0.3 nm and 1 nm.
[0177] In one embodiment, the composition has the general formula [Sc 3 O(OH)(BTC) 2 ], where BTC is benzene-1,3,5-tricarboxylic acid.
[0178] In one embodiment, the molecule Y is propylene oxide.
[0179] In one embodiment, the polymer formed is a polycarbonate-polyether copolymer.
[0180] In one embodiment, the process is carried out at a temperature between 45°C and 65°C.
[0181] In one embodiment, the process is carried out at a pressure between 0.1 MPa and 10 MPa.
[0182] In one embodiment, the polymer formed is a polyether or a polyester.
[0183] In yet another aspect of the present invention, a polymer is provided. The polymer is obtainable or obtained according to the above method of the present application.
[0184] In one embodiment, the polymer is a polycarbonate-polyether copolymer having greater than 95% incorporation of carbonate linkages.
[0185] In one embodiment, the polymer has a number average molecular weight (M) of less than 10 kDa. n ) polymer.
[0186] In yet another aspect of the present invention, a method for forming a cyclic carbonate is provided, wherein CO 2 is incorporated into the structure of a cyclic carbonate, the method comprising reacting the molecule Y' with CO in the presence of a composition 2 The reaction composition comprises:
[0187] The bulk material; and
[0188] at least one surface;
[0189] The bulk material includes ions of metal M bonded to each other via linker groups;
[0190] The surface comprises ions of metal M' bonded to each other via linker groups;
[0191] Metal M and metal M' are the same or different;
[0192] The surface comprises at least one first site A and at least one second different site B;
[0193] Site A has a hydroxyl group -X bonded thereto;
[0194] Site B is able to interact with CO in a certain way 2 The Lewis acid sites of the molecules interact in such a way that CO 2 Orienting the molecule so as to facilitate reaction with molecule Y';
[0195] Site B has a Lewis base bound to it;
[0196] The distance d' between site A and site B is such that the molecule Y' and the adsorbed CO 2 can react together on the surface to form a cyclic carbonate. BRIEF DESCRIPTION OF THE DRAWINGS
[0197] Figure 1 The figure shows the surface structure of the hybrid platform catalyst composition and the general structure of the bulk material according to one embodiment of the present invention, wherein the metal ion M and the metal ion M' are connected by a trivalent linker and an unoccupied Lewis acid site B is shown;
[0198] Figure 2 The figure shows the surface structure and the general structure of the bulk material of a hybrid platform catalyst composition according to another embodiment of the present invention, wherein the metal ion M and the metal ion M' are connected by a trivalent linker, and the non-coordinating group R' forms a part of the linker group;
[0199] Figure 3 The figure shows the surface structure of the hybrid platform catalyst composition and the general structure of the bulk material according to one embodiment of the present invention, wherein the metal ion M and the metal ion M' are connected by a divalent linker and an unoccupied Lewis acid site B is shown;
[0200] Figure 4 The figure shows the surface structure of the hybrid platform catalyst composition and the general structure of the bulk material according to one embodiment of the present invention, wherein the metal ion M and the metal ion M' are connected by a divalent linker and shows that the Lewis acid site B is combined with the divalent Lewis base D;
[0201] Figure 5 is a pair distribution function plot from a total scattering experiment of the composition according to Example 1 of the present invention;
[0202] Figure 6 is the composition according to Example 1 of the present invention 45 Sc magic angle spinning (MAS) NMR spectroscopy;
[0203] Figure 7 is a nitrogen physical adsorption graph showing the specific surface area of the composition according to Example 1 of the present invention;
[0204] Figure 8 is a scanning electron microscope (SEM) image of the composition according to Example 1 of the present invention;
[0205] Fig. 9 is a transmission electron microscope (TEM) image of the composition according to Example 1 of the present invention;
[0206] Fig.10 Graph showing selectivity of a composition according to one embodiment of the present invention (for production of polycarbonate-polyether copolymers relative to cyclic carbonates) compared to a Robson-type homogeneous catalyst and a zinc glutarate heterogeneous catalyst;
[0207] Fig.11 The graph shows the turnover frequency of a composition according to one embodiment of the present invention compared to a Robson-type homogeneous catalyst and a zinc glutarate heterogeneous catalyst, defined as: (mass of polymer) / (mass of active metal in catalyst*reaction time);
[0208] Fig.12 is a transmission electron microscope (TEM) image of composition 1 according to Example 4 of the present invention;
[0209] Fig.13 is a transmission electron microscope (TEM) image of composition 2 according to Example 4 of the present invention;
[0210] Fig.14 is a transmission electron microscope (TEM) image of composition 3 according to Example 4 of the present invention;
[0211] Fig.15 is a transmission electron microscope (TEM) image of the composition according to Example 4 of the present invention;
[0212] Fig.16 is a transmission electron microscopy (TEM) image of a control composition described in Example 4 without a modulator; and
[0213] Fig.17 A computational model of a composition according to the invention is shown, showing the A-site to which the hydroxyl group is bound and the B-site with one coordination site vacant.
[0214] Details
[0215] Advantages and surprising findings
[0216] The present inventors have surprisingly discovered that it is possible to produce compositions of the present invention having surfaces in which hydroxyl-binding sites (also described herein as "A-sites") are present on the surface at sufficient density and in sufficient proximity to Lewis acidic sites (also described hereinafter as "B-sites") on the surface such that, in use, both the A-sites and the B-sites can participate in catalytic activity. These favorable surface properties enable their use as hybrid platform catalysts for a range of reactions, particularly those involving the conversion of CO 2 The unit is inserted into the structure of the molecule, allowing CO 2 use.
[0217] The present inventors have surprisingly found that the compositions of the present invention can be used to catalyze polymerization reactions under much milder conditions than those disclosed in the prior art, wherein CO 2 are incorporated into the structure of polymers, for example from epoxides (such as propylene oxide) and CO 2 In particular, the reaction can be carried out at lower temperatures, lower pressures and for much shorter reaction times than disclosed in the prior art. It also provides a higher selectivity for producing polycarbonate-polyether copolymers relative to producing cyclic carbonates, with comparable carbonate bonds in the polymer backbone.
[0218] In particular, it has surprisingly been found that the surface properties of the composition of the invention enable it to catalyze polymerization reactions in which CO 2 are incorporated into the structure of polymers, for example from epoxides (such as propylene oxide) and CO 2 Polycarbonate-polyether copolymer, in which a large amount of CO 2 Insertion is possible such that a high percentage of carbonate bonds are incorporated into the polymer.
[0219] Furthermore, the inventors have surprisingly discovered that incorporating a modulator (as defined and exemplified below) into the compositions of the present invention, particularly using a specific molar ratio of modulator and source of linker groups, enables the compositions to be produced with better control over crystallite size and particle morphology than has been demonstrated in the prior art.
[0220] Furthermore, it has been surprisingly found that the compositions thus produced are capable of catalyzing polymerization reactions, in particular in which CO 2 Polymerization reactions that are incorporated into the structure of a polymer, wherein the polymer so produced has a lower average molecular weight (Mn), typically less than 10 kDa, than is possible when those reactions are carried out using catalysts of the prior art. Polymers having such molecular weights are more commercially useful than corresponding higher molecular weight polymers produced in the art.
[0221] definition
[0222] As used herein, the term "crystal" generally means a small single crystal (i.e., a small single solid material in which the crystal lattice of the material is continuous and unbroken and has no grain boundaries). Single crystalline material should be contrasted with polycrystalline material or agglomerate material, which includes a collection of crystals adhered together. Typically, the size of such crystallites ranges from 1 nm to 1 μm, preferably 1 nm to 100 nm.
[0223] As used herein, the term "modifier" means a small organic molecule that can be combined with a metal ion. A modifier is an organic molecule different from the organic molecule that provides a source of a linker group. Typically, a modifier has a molecular weight of 30Da to 900Da. In one embodiment, a modifier has a molecular weight of 40Da to 750Da. In one embodiment, a modifier has a molecular weight of 50Da to 600Da. In one embodiment, a modifier has a molecular weight of 60Da to 500Da. In one embodiment, a modifier has a molecular weight of 70Da to 400Da. In one embodiment, a modifier has a molecular weight of 80Da to 350Da. In one embodiment, a modifier has a molecular weight of 90Da to 300Da. In one embodiment, a modifier has a molecular weight of 100Da to 250Da. In one embodiment, a modifier has a molecular weight of 60Da to 180Da. In one embodiment, a modifier has a molecular weight of 100Da to 170Da. In one embodiment, a modifier has a molecular weight of 110Da to 200Da.
[0224] As used herein, "alkyl" means a straight or branched saturated aliphatic group containing only carbon and hydrogen, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl and neopentyl. The alkyl group can be unsubstituted or substituted with one or more substituents, as described below. In some embodiments, the alkyl group includes 1 to 8 carbon atoms (e.g., 1 to 6 carbon atoms, 1 to 4 carbon atoms, or 1 to 2 carbon atoms).
[0225] As used herein, "alkenyl" means a straight or branched aliphatic group comprising only carbon and hydrogen and at least one carbon-carbon double bond, such as vinyl, 1-propenyl, 2-propenyl, 2-methyl-1-propenyl, 1-butenyl, 2-butenyl and similar groups. In various embodiments, alkenyl groups can be unsubstituted or substituted with one or more substituents, as described below. Typically, alkenyl groups will include 2 to 8 carbon atoms (for example, 2 to 6 carbon atoms, 2 to 4 carbon atoms or 2 carbon atoms).
[0226] As used herein, "alkynyl" means a straight or branched aliphatic group containing only carbon and hydrogen and containing at least one carbon-carbon triple bond, such as ethynyl, 1-propynyl, 1-butynyl, 2-butynyl and similar groups. In various embodiments, the alkynyl group can be unsubstituted or substituted with one or more substituents. Typically, the alkynyl group will contain 2 to 8 carbon atoms (e.g., 2 to 6 carbon atoms, 2 to 4 carbon atoms, or 2 carbon atoms).
[0227] As used herein, "alkylene" means a divalent branched or straight chain saturated group comprising only carbon and hydrogen, such as methylene, ethylene, n-propylene, isopropylene, n-butylene, isobutylene, secondary butylene, tert-butylene, n-pentylene, isopentylene, secondary pentylene and neopentylene. The alkylene group may be unsubstituted or substituted with one or more substituents. In some embodiments, the alkylene group includes 1 to 8 carbon atoms (e.g., 1 to 6 carbon atoms, 1 to 4 carbon atoms or 1 to 2 carbon atoms).
[0228] As used herein, "alkenylene" means a divalent branched or straight chain group comprising only carbon and hydrogen and at least one carbon-carbon double bond, such as vinylene, 1-propenylene, 2-propenylene, 2-methyl-1-propenylene, 1-butenylene, 2-butenylene and similar groups. In various embodiments, the alkenylene group can be unsubstituted or substituted with one or more substituents. Typically, the alkenylene group will include 2 to 8 carbon atoms (e.g., 2 to 6 carbon atoms, 2 to 4 carbon atoms or 2 carbon atoms).
[0229] As used herein, "alkynylene" means a divalent branched or straight chain chemical group containing only carbon and hydrogen and containing at least one carbon-carbon triple bond, such as ethynylene, 1-propynylene, 1-butynylene, 2-butynylene and similar groups. In various embodiments, the alkynylene group can be unsubstituted or substituted with one or more substituents. Typically, the alkynylene group will contain 2 to 8 carbon atoms (e.g., 2 to 6 carbon atoms, 2 to 4 carbon atoms, or 2 carbon atoms).
[0230] As used herein, "cycloalkyl" means a saturated cyclic ring system containing only carbon atoms in the ring system backbone, such as cyclopropyl, cyclobutyl, cyclopentyl and cyclohexyl. In some embodiments, the cycloalkyl group includes 3 to 10 carbon atoms, for example 3 to 6 carbon atoms.
[0231] As used herein, "heterocyclyl" means a non-aromatic cyclic ring system containing at least one heteroatom in the ring system backbone. The heterocyclyl may include multiple fused rings. The heterocyclyl may be substituted with one or more substituents or may be unsubstituted. In some embodiments, the heterocycle has 3-11 members. In a six-membered monocyclic heterocycle, the heteroatom is selected from one to three of O, N or S, and wherein when the heterocycle is five-membered, it may have one or two heteroatoms selected from O, N or S. Examples of heterocyclic groups include azirinyl, aziridinyl, azetidinyl, oxetanyl, thietanyl, 1,4,2-dithiazolyl, dihydropyridinyl, 1,3-dioxanyl, 1,4-dioxanyl, 1,3-dioxolanyl, morpholinyl, piperazinyl, pyranyl, pyrrolidinyl, tetrahydrofuranyl, tetrahydropyridinyl, oxazinyl, thiazinyl, thienyl, thiazolidinyl, isothiazolidinyl, oxazolidinyl, isoxazolidinyl, piperidinyl, pyrazolidinyl, imidazolidinyl, and thiomorpholinyl.
[0232] As used herein, "aryl" means a monocyclic, bicyclic, tricyclic or polycyclic group having only carbon atoms present in a ring skeleton having 5 to 14 ring atoms (preferably 5, 6, 9 or 10 ring atoms) and 6, 10 or 14 π electrons shared in a cyclic array; wherein at least one ring in the system is aromatic. The aryl group may be unsubstituted or substituted with one or more substituents. Examples of aryl include phenyl, naphthyl, tetrahydronaphthyl and biphenyl. In some embodiments, aryl is phenyl.
[0233] As used herein, the term "heteroaryl" means a monocyclic, bicyclic, tricyclic or polycyclic group having 5 to 14 ring atoms (preferably 5, 6, 9 or 10 ring atoms) and 6, 10 or 14 π electrons shared in a cyclic array; wherein at least one ring in the system is aromatic, and at least one ring in the system contains one or more heteroatoms independently selected from the group consisting of N, O and S. Heteroaryl groups may be unsubstituted or substituted with one or more substituents. Examples of heteroaryl groups include thienyl, pyridyl, furanyl, oxazolyl, oxadiazolyl, pyrrolyl, imidazolyl, triazolyl, thiodiazolyl, pyrazolyl, isoxazolyl, thiadiazolyl, pyranyl, pyrazinyl, pyrimidinyl, pyridazinyl, triazinyl, thiazolyl, benzothienyl, benzoxadiazolyl, benzofuranyl, benzimidazolyl, benzotriazolyl, cinnolinyl, indazolyl, indolyl, isoquinolyl, isothiazolyl, naphthyridinyl, purinyl, thienopyridinyl, pyrido[2,3-d]pyrimidinyl, pyrrolo[2,3-d]pyrimidinyl, d]pyridinyl, quinazolinyl, quinolinyl, thieno[2,3-c]pyridinyl, pyrazolo[3,4-b]pyridinyl, pyrazolo[3,4-c]pyridinyl, pyrazolo[4,3-c]pyridinyl, pyrazolo[4,3-b]pyridinyl, tetrazolyl, chromanyl, 2,3-dihydrobenzo[b][1,4]dioxin, benzo[d][1,3]dioxole, 2,3-dihydrobenzofuran, tetrahydroquinoline, 2,3-dihydrobenzo[b][1,4]oxathiin and others. In some embodiments, heteroaryl is selected from thienyl, pyridinyl, furanyl, pyrazolyl, imidazolyl, pyranyl, pyrazinyl and pyrimidinyl.
[0234] As used herein, "halo", "halide" or "halogen" is a chlorine radical, a bromine radical, a fluorine radical or an iodine radical. In some embodiments, the halo is chlorine, bromine or fluorine. For example, the halide can be fluorine.
[0235] The term "substituted" refers to a moiety having substituents replacing hydrogen atoms on one or more non-hydrogen atoms of a molecule. It should be understood that "substituted" or "substituted with" includes the implicit proviso that such substitution is in accordance with the allowed valencies of the substituted atom and the substituent, and that the substitution results in a stable compound, e.g., it does not spontaneously undergo transformations such as by rearrangement, cyclization, elimination, etc. Substituents may include, for example, hydroxy, -NH 2 、-NH(C 1-3 Alkyl) and -N(C 1-3 alkyl) 2 One or more optionally substituted -(C 1-8 Alkyl); -(C 1-9haloalkyl); halide; hydroxyl; carbonyl [such as -C(O)OR and -C(O)R]; thiocarbonyl [such as -C(S)OR, -C(O)SR and -C(S)R]; halide, hydroxyl, -NH 2 、-NH(C 1-3 Alkyl) and -N(C 1-3 alkyl) 2 One or more optionally substituted -(C 1-8 Alkoxy); -OPO(OH) 2 ; Phosphonates [such as -PO(OH) 2 and-PO(OR') 2 ]; -OPO(OR')R"; -NRR'; -C(O)NRR'; -C(NR)NR'R"; -C(NR')R"; cyano; nitro; azido; -SH; -SR; -OSO 2 (OR); sulfonate [such as -SO 2 (OH) and -SO 2 (OR)]; -SO 2 NR'R"; and -SO 2 R; wherein R, R' and R" are independently selected at each occurrence from H and -(C 1-8 alkyl).
[0236] Composition
[0237] In one aspect of the present invention, there is provided a composition comprising:
[0238] The bulk material; and
[0239] at least one surface;
[0240] The bulk material includes ions of metal M bonded to each other via linker groups;
[0241] The surface comprises ions of metal M' bonded to each other via linker groups;
[0242] Metal M and metal M' are the same or different;
[0243] The surface comprises at least one first site A and at least one second different site B;
[0244] Site A has a hydroxyl group bonded thereto, said site A optionally being capable of bonding to a CO 2 interaction;
[0245] Site B is capable of binding CO 2 Lewis acidic sites of the molecule;
[0246] The distance d between site A and site B is such that the monomer molecule Y and the bound CO 2 can react together on the surface to form a polymer where CO 2 are incorporated into the structure of the polymer.
[0247] In one aspect of the present invention, there is provided a composition comprising:
[0248] bulk material; and
[0249] at least one surface;
[0250] The bulk material includes ions of metal M bonded to each other via linker groups;
[0251] The surface comprises ions of metal M' bonded to each other via linker groups;
[0252] Metal M and metal M' are the same or different;
[0253] The surface comprises at least one first site A and at least one second different site B;
[0254] Site A has a hydroxyl group bonded thereto, said site A being capable of interacting with a monomer molecule;
[0255] Site B is a Lewis acidic site, and the site B can interact with a monomer molecule;
[0256] The composition is obtainable by reacting a source of metal ions M and a source of metal ions M' with a source of linker groups and a source of hydroxyl groups in the presence of a modulator under conditions such that the surface of the composition has a first site A to which hydroxyl groups are attached and a second site B that is Lewis acidic.
[0257] In one aspect of the present invention, there is provided a microcrystalline composition comprising:
[0258] bulk material; and
[0259] at least one surface;
[0260] The bulk material includes ions of metal M bonded to each other via linker groups;
[0261] The surface comprises ions of metal M' bonded to each other via linker groups;
[0262] Metal M and metal M' are the same or different;
[0263] The surface comprises at least one first site A and at least one second different site B;
[0264] Site A has a hydroxyl group bonded thereto, said site A being capable of interacting with a monomer molecule;
[0265] Site B is a Lewis acidic site, which is capable of interacting with a monomer molecule.
[0266] In one embodiment, the composition of the invention is a microcrystalline composition (as defined herein). Compared to compositions produced using prior art methods (which produce particles in the form of agglomerates comprising collections of microcrystals), the use of a modifier according to the method of the invention enables the production of compositions in the form of individual single crystals with control over the crystallite size and particle morphology.
[0267] In one embodiment, the average size of the crystallites is between 1 nm and 100 nm. In one embodiment, the average size of the crystallites is between 10 nm and 80 nm.
[0268] The composition of the invention comprises a bulk material. Typically, the bulk material comprises ions of a metal M bonded to each other via linker groups, thereby forming a framework or scaffold.
[0269] The metal M can be any metal capable of forming an ion with which the linker group can coordinate to form the bulk material. Examples of such metals include transition metals, including first row transition metals such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn, second row transition metals such as Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, and Cd, third row transition metals such as Hf, Ta, W, Re, Os, Ir, Pt, Au, and Hg; lanthanides such as La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; and p-block metals such as Al, Ga, Ge, In, Sn, Tl, Pb, and Bi.
[0270] The metal ions M coordinated to the linker group to form the bulk material may be the same or different. In one embodiment, the bulk material comprises ions of only one metal M. In another embodiment, the bulk material comprises ions of a mixture of more than one (preferably 2 to 4, more preferably 2 or 3, most preferably 2) different metals M. .
[0271] In relation to CO 2 When used in an incorporated polymerization reaction, as described in more detail below, the function of the hydroxyl groups on the surface of the catalyst is to interact with monomer molecules Y or molecules Y', CO 2In the final product, it is incorporated into the monomer molecule Y or molecule Y'. In particular, when the molecule Y or Y' is an epoxide, the -OH group on the surface of the composition of the present invention promotes the ring opening of the epoxide group so that it can react with CO on the surface of the catalyst. 2 In addition, site A is optionally capable of reacting with CO 2 Interaction. The surface of the composition of the present invention is provided with a sufficient number of hydroxyl groups that are sufficiently close to the B-sites on the surface to enhance the activity of the catalyst for copolymerization or cyclic carbonate formation reactions.
[0272] Site B is a Lewis acid site. In this specification, "Lewis acid" takes its usual meaning in the field of electron pair acceptors. Depending on the intended use of the composition, Lewis acid site B can be vacant (unoccupied) or can have a Lewis base bound to it.
[0273] In one embodiment, site B is capable of interacting with a monomer molecule. In one embodiment, site B is capable of interacting with a CO 2 In one embodiment, site B is capable of interacting with a monomer molecule and with CO 2 The two interact with each other.
[0274] In one embodiment, the Lewis acidic site B is unoccupied. In this embodiment, the metal ion is therefore coordinatively unsaturated. "Coordinatively unsaturated" means that not all of the usual coordination sites of the metal ion are occupied. Typically, 1, 2 or 3, in one embodiment 1 or 2, in one embodiment 1 coordination site is unoccupied. By way of example, in a metal ion having the general formula [Sc 3 O(OH)(BTC) 2 In a particularly preferred case of a compound of ], a Sc having a site B on the surface 3+ The ion is 5-coordinated instead of the usual 6-coordinated.
[0275] In relation to CO 2 In the polymerization reaction, as described in more detail below, the function of the unoccupied Lewis acidic sites B is to bind CO 2 molecules, making the combined CO 2 The molecules interact with monomer molecules Y to form a polymer in which the bound CO 2 is incorporated into the polymer structure. Lewis acids promote CO 2 In particular, when molecule Y is an epoxide, the presence of unoccupied Lewis acidic sites on the surface of the composition of the present invention promotes the incorporation of CO 2Reaction with ring-opened epoxy groups on the catalyst surface.
[0276] In one embodiment, the Lewis acidic site B has a Lewis base bound thereto. The term "Lewis base" has its usual meaning in the art of any compound having at least one (such as one, two or three) Lewis bases, i.e., groups that donate electron pairs. Lewis basic groups are well known to those skilled in the art and include oxygen-based electron pair donors such as -OH and -OR, amino groups such as -NH 2 、-NH(C 1-6 Alkyl) and -N(C 1-6 alkyl) 2 Examples of Lewis bases include alcohols such as C 1-6 Alcohols, including diols, especially C 2-6 Alkylene glycols such as ethylene glycol and propylene glycol; amines such as (C 1-6 Alkyl)amine, di(C 1-6 Alkyl)amine and C 2-6 Alkylene diamines such as ethylene diamine; C 2-6 Alkyleneamino alcohols, such as ethanolamine, and heterocyclyl groups and heteroaryl groups as defined and exemplified above (eg piperazine or imidazole).
[0277] In use, as described in more detail below, the Lewis acidic site B having a Lewis base bound thereto functions to allow CO 2 The reaction of molecules with molecules Y' is promoted in the same way as CO 2 The molecules interact to form molecules where CO 2 In particular, when the molecule Y' is an epoxide, the presence of the bound Lewis acidic B-sites on the surface of the composition of the present invention promotes CO binding to the A-sites. 2 Reacts with the ring-opened epoxy groups on the surface of the catalyst to form cyclic carbonates.
[0278] Figure 1 The figure shows the surface structure of a composition according to one embodiment of the present invention and the general structure of the bulk material. In this embodiment, the metal ion M and the metal ion M' are connected by a trivalent linker. The surface metal ion M' is labeled A and B to illustrate the difference between the sites. In this embodiment, the Lewis acid site B is unoccupied. The distance d between the A site and the B site is important, as explained in more detail below. When used to catalyze CO 2 is incorporated into the structure of the polymer during polymerization, including CO 2 The ratio of the incorporated repeating units (e.g., carbonate repeating units) is compared to the ratio of the lack of CO 2The proportion of incorporated repeat units (eg ether repeat units) is much greater.
[0279] Figure 2 The figure shows the surface structure of the composition according to another embodiment of the present invention and the general structure of the bulk material. In this embodiment, the metal ion M and the metal ion M' are connected by a trivalent linker. This is similar to Figure 1 The difference shown in the figure is that the non-coordinating group R' forms part of the linker group. Although this maintains the distance d between the A site and the B site, the attachment of the group R' enables the surface properties of the composition and its catalytic properties to be adjusted to catalyze the reaction with Figure 1 The results are different from those of the reactions described in more detail below. For example, when used to catalyze the 2 is incorporated into the structure of the polymer during polymerization, where Figure 1 Compared with those, including CO 2 The proportion of incorporated repeat units (e.g. carbonate repeat units) is reduced, which favors the lack of CO 2 Incorporated repeating units (eg, ether repeating units).
[0280] Figure 3 The figure shows the surface structure of a composition according to one embodiment of the present invention and the general structure of the bulk material, wherein the metal ion M and the metal ion M' are connected by a divalent linker and an unoccupied Lewis acid center B is shown. In this embodiment, the distance d" between the A site and the B site is larger. This general structure is generally less conducive to catalysis of CO 2 The polymerization reaction is incorporated into the structure of the polymer because it includes CO 2 The resulting ratio of the incorporated repeating units (e.g., carbonate repeating units) is compared to the ratio of the incorporation of CO 2 The proportion of incorporated repeat units (eg ether repeat units) is much smaller.
[0281] The distance between site A and site B on the surface of the composition of the present invention is important because the sites must be close enough together to allow the bound CO to form a bonded 2 The molecule with CO 2 The incorporated molecule Y or molecule Y' interacts.
[0282] In one embodiment, the surface of the composition of the present invention is configured such that the bound CO 2 can be incorporated into the structure of the polymer. In this embodiment, the distance between the metal atom carrying the hydroxyl group at site A and the metal atom at site B (in Figure 1 and Figure 2d) such that the monomer molecule Y (particularly but not exclusively an epoxide) and the bound CO 2 can react together on the surface to form a polymer where CO 2 is incorporated into the structure of the polymer. The distance d may vary depending on the nature of the monomer Y, the linker group and the metal ion M' on the surface. In one embodiment, the distance d is between 0.3 nm and 1 nm.
[0283] The distance d between the metal atoms at site A and site B can be measured by a number of techniques known to those skilled in the art.
[0284] In one embodiment, the distance d can be calculated based on solid-state NMR measurements, for example using the method described in S. Hayashi and K. Hayamizu, Bull. Chem. Soc. Jpn., 1991, 64, 685-687 and chemical shift standards.
[0285] In one embodiment, the distance d can be determined based on crystallographic data by means of a suitable calculation method. As known to those skilled in the art, suitable crystallographic methods for obtaining data include X-ray crystallography. One such suitable X-ray crystallographic method is powder diffraction (PDF) analysis. A specific method for performing PDF analysis is shown below.
[0286] In this specific example, the PDF analysis is performed on a The image was taken on a Rigaku R-Axis3-circle Spider goniometer. The image board is mounted in a graphite monochrome sealed tube silver operated at 1.2kW (40kV, 30mA) The window of the generator. A borosilicate capillary with a diameter of 1 mm and a wall thickness of 0.01 mm was used. The fixed distance from the capillary to the detector was 127.4 mm, and the exposure time per oscillation ω degree was 84 s. An oscillation ω of 84 ° was used, giving a total collection time of 117.6 minutes. The collected 2D powder images were integrated into a 1D total scattering map using Rigaku2DP software and converted to a pair distribution function using GudrunX. This is described in more detail in Billinge, SJLZ Für Krist.-Cryst.Mater.2004,219(3),117-121, and in Egami, T. and Billinge, SJL Underneath the Bragg Peaks:Structural Analysis of ComplexMaterials, Second Edition; Pergamon Materials Series; Elsevier: Amsterdam, 2012.
[0287] After the crystallographic data have been obtained, the distance d can be obtained from these data using a suitable calculation method. An example of such a calculation method uses density functional theory (DFT). As known to those skilled in the art, in the context of computational materials science, ab initio (from first principles) DFT calculations allow prediction and calculation of material behavior based on quantum mechanical considerations without the need for higher order parameters such as basic material properties. In contemporary DFT techniques, the electronic structure is evaluated using the potential acting on the electrons of the system. The DFT potential is constructed as an external potential V ext and effective potential V eff The sum of the external potential V ext Determined only by the structure and element composition of the system, the effective potential V eff represents the interaction between electrons. Therefore, the problem of a representative supercell of a material with n electrons can be expressed as a set of n one-electron Schrödinger-like equations. -like equation), the single-electron Schrödinger-like equation is also known as the Kohn-Sham equation, as described, for example, in Hanaor, D. et al. Computational Mechanics. 2012 50(2): 185–194.
[0288] By way of example, interatomic distances can be calculated using the Gaussian 16 program at the density functional theory (DFT) level with a hybrid functional B3LYP, as described in MJ Frisch, et al., Gaussian 16 Rev. B. 01, Wallingford, CT, 2016 and in AD Becke, J. Chem. Phys., 1993, 98, 5648-5652. For light atoms, Dunning's related consistent cc-pVDZ basis set can be used. Metal atoms can be described by effective core potentials and related basis sets, as described in PJ Hay and WR Wadt, J. Chem. Phys., 1985, 82, 299-310. Dispersion can be included in all calculations using the atom-atom semi-empirical method and parameters proposed by Grimme et al., J. Chem. Phys., 2010, 132, 154104. When calculating the coordination energies, a Boys equilibrium correction was used to compensate for the basis set superposition error (BSSE).
[0289] Fig.17 The molecular structure of the composition according to the present invention is shown by means of a computational model, showing an A-site with a hydroxyl group bound thereto and a B-site in which one of the coordination sites is vacant. The distance d between the A-site and the B-site can be calculated using the methods generally and specifically described above.
[0290] In one embodiment, the surface of the composition of the present invention is configured such that the bound CO 2 can be incorporated into the structure of the cyclic carbonate. In this embodiment, the distance d' between site A and site B is such that the molecule Y' and the bound CO 2 The distance d' may vary depending on the nature of the monomer Y', the linker group and the metal ion M' on the surface, but is generally longer than the distance d of the catalyst, which is configured to promote the monomer molecule Y (particularly but not exclusively epoxide) and the bound CO 2 to form a polymer, where CO 2 is incorporated into the structure of the polymer. In one embodiment, the distance d' is between 0.3 nm and 1.3 nm.
[0291] Figure 4 The figure shows the surface structure of the composition according to this embodiment of the present invention and the general structure of the bulk material, wherein the metal ion M and the metal ion M' are connected by a divalent linker and the Lewis acid site B to which the Lewis base D is bound is shown. In this embodiment, the distance d' between the A site and the B site is greater than Figure 1 and Figure 2However, the presence of a Lewis base D allows the 2 interaction in order to promote the reaction with the molecule Y'. This allows to overcome the Figure 3 The distance between the A site and the B site in the reaction mixture makes the composition useful as a catalyst for the catalysis of epoxides and CO 2 to produce a cyclic carbonate, where CO 2 is incorporated into the structure of the cyclic carbonate.
[0292] Method of producing a composition
[0293] The present invention also provides a method for producing the composition of the present invention. Typically, such a method comprises reacting a source of metal ions M and a source of metal ions M' with a source of linker groups and a source of hydroxyl groups and a modifier, and subjecting the composition to conditions such that the surface of the composition has a first site A to which hydroxyl groups are bound and a second site B that is Lewis acidic.
[0294] The source of metal ions M and the source of metal ions M' may be any substance capable of producing the metal M and the metal M' in the necessary ionic form. Typically, these include metal salts in which the metal is in ionic form with a suitable counterion, examples of which include halides (fluorides, chlorides, bromides, iodides), hydroxides, alkoxides, sulfates, nitrates, phosphates, alkyl sulfonates, aryl sulfonates, alkyl phosphonates, aryl phosphonates (the alkyl and aryl portions of these counterions are as defined and exemplified above).
[0295] The linker group source can be any substance that can produce the linker group, and the linker group is in a form that can coordinate with the metal ion. In one embodiment, the linker group source includes such a compound, and the compound is the conjugate acid of the linker group as present in the final composition, so that the linker group coordinated with the metal ion is its conjugate base (that is, it differs from the compound as the linker group source by at least 1 proton, preferably 1, 2 or 3 protons). Typically, in this embodiment, the linker group source is an organic acid, such as a carboxylic acid. In one embodiment, the linker group source is a dicarboxylic acid. In one embodiment, the linker group source is a tricarboxylic acid.
[0296] The source of hydroxyl groups can be any compound capable of reacting so as to produce a composition in which hydroxyl groups are present at site A on the surface of the composition. Examples of such a source include water.
[0297] In one embodiment, a modifier is added to the composition. According to the present invention, the addition of a modifier to the reaction mixture facilitates the formation of a composition having the surface properties described herein, which makes the composition particularly active as a catalyst, especially for catalyzing CO 2 Without wishing to be bound by theory, it is believed that the modulator binds to the metal salt used in the synthesis and competes with the linker during formation of the composition.
[0298] In one embodiment, the metal ion M and the metal ion M' are the same, and the conditioning agent is added to the composition. In one embodiment, the metal ion M and the metal ion M' are both Sc 3+ , and a conditioning agent is added to the composition.
[0299] In one embodiment, a modifier is not added to the composition. In one embodiment, the metal ion M and the metal ion M' are different and a modifier is not added to the composition.
[0300] In one embodiment, the stoichiometric ratio of the metal ion source to the modifier is between 1:0.001 and 1:1000. In one embodiment, the stoichiometric ratio of the metal ion source to the modifier is between 1:0.1 and 1:500. In one embodiment, the stoichiometric ratio of the metal ion source to the modifier is between 1:0.2 and 1:250. In one embodiment, the stoichiometric ratio of the metal ion source to the modifier is between 1:0.4 and 1:150.
[0301] The modulator can be any small molecule that is capable of binding to the metal ion while being easily removable from the final composition (e.g., by washing) such that it is present in only small amounts or not in the final composition. In one embodiment, the modulator has a molecular weight lower than that of the source of the linker group.
[0302] Typical possible regulators include organic acids (including but not limited to carboxylic acids, phosphonic acids, phosphoric acids, phosphinic acids, sulfonic acids, sulfinic acids, sulfenic acids), alcohols and amines.
[0303] In one embodiment, the regulator is an aliphatic compound having a total of 1 to 20 carbon atoms. In one embodiment, the regulator is an aliphatic compound having a total of 1 to 10 carbon atoms. In one embodiment, the regulator is an aliphatic compound having a total of 1 to 8 carbon atoms. In one embodiment, the regulator is an aliphatic compound having a total of 1 to 6 carbon atoms. In one embodiment, the regulator is an aliphatic compound having a total of 1 to 4 carbon atoms. In one embodiment, the regulator is an aliphatic compound having a total of 1 to 3 carbon atoms. In one embodiment, the regulator is an aliphatic compound having a total of 2 carbon atoms.
[0304] In one embodiment, the modifier is an aromatic compound having a total of 6 to 20 carbon atoms. In one embodiment, the modifier is an aromatic compound having a total of 6 to 10 carbon atoms. In one embodiment, the modifier is an aromatic compound having a total of 6 to 8 carbon atoms. The aryl portion of the aromatic compound can be substituted as defined and exemplified above for aryl groups.
[0305] In one embodiment, the modifier is an organic acid. In one embodiment, the modifier is added to the composition as a free acid. In another embodiment, the modifier is generated in situ by reaction of the conjugate base of the acid with a stronger acid. In another embodiment, the modifier is generated in situ by reduction of the corresponding peroxy acid (i.e., an organic acid in which at least one of the hydroxyl moieties of the acid functional group is replaced by the group -OOH) with a suitable reducing agent.
[0306] In one embodiment, the regulator is a carboxylic acid. In one embodiment, the regulator is a carboxylic acid with a total of 1 to 20 carbon atoms. In one embodiment, the regulator is an aliphatic carboxylic acid with 1 to 20 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is a carboxylic acid with a total of 1 to 10 carbon atoms. In one embodiment, the regulator is an aliphatic carboxylic acid with 1 to 10 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic carboxylic acid with a total of 1 to 8 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic carboxylic acid with a total of 1 to 6 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic carboxylic acid with a total of 1 to 4 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic carboxylic acid with a total of 2 to 4 carbon atoms, which can be substituted by 1 to 7 halogen atoms. In one embodiment, regulator is an aliphatic carboxylic acid with 1 to 3 carbon atoms, which can be replaced by one or more halogen atoms. In one embodiment, regulator is an aliphatic carboxylic acid with 2 or 3 carbon atoms, which can be replaced by 1 to 5 halogen atoms. In one embodiment, regulator is an aliphatic carboxylic acid with 2 carbon atoms, which can be replaced by one or more halogen atoms. In one embodiment, regulator is an aliphatic carboxylic acid with 2 carbon atoms, which can be replaced by one or more halogen atoms. In one embodiment, regulator is an aliphatic carboxylic acid with 2 carbon atoms, which can be replaced by 1, 2 or 3 halogen atoms. In these embodiments, halogen atoms can be the same or different. Preferably, halogen atoms are selected from fluorine or chlorine. In one embodiment, regulator is selected from the group consisting of trifluoroacetic acid, trichloroacetic acid and acetic acid.
[0307] In another embodiment, the regulator is an aromatic carboxylic acid having a total of 6 to 20 carbon atoms. In another embodiment, the regulator is an aromatic carboxylic acid having a total of 6 to 10 carbon atoms. In one embodiment, the regulator is an aromatic carboxylic acid having a total of 6 to 8 carbon atoms. The aryl moiety of the aromatic compound can be substituted as defined and exemplified above for the aryl group. In one embodiment, the regulator is benzoic acid.
[0308] In one embodiment, the regulator is a sulfonic acid. In one embodiment, the regulator is a sulfonic acid with a total of 1 to 20 carbon atoms. In one embodiment, the regulator is an aliphatic sulfonic acid with 1 to 20 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is a sulfonic acid with a total of 1 to 10 carbon atoms. In one embodiment, the regulator is an aliphatic sulfonic acid with 1 to 10 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic sulfonic acid with a total of 1 to 8 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic sulfonic acid with a total of 1 to 6 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic sulfonic acid with a total of 1 to 4 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic sulfonic acid with 1 to 3 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the modifier is an aliphatic sulfonic acid having 2 carbon atoms, which may be substituted with one or more halogen atoms.
[0309] In another embodiment, the modifier is an aromatic sulfonic acid having a total of 6 to 20 carbon atoms. In another embodiment, the modifier is an aromatic sulfonic acid having a total of 6 to 10 carbon atoms. In one embodiment, the modifier is an aromatic sulfonic acid having a total of 6 to 8 carbon atoms. The aryl portion of the aromatic compound can be substituted as defined and exemplified above for the aryl group.
[0310] In one embodiment, the regulator is a sulfinic acid. In one embodiment, the regulator is a sulfinic acid with a total of 1 to 20 carbon atoms. In one embodiment, the regulator is an aliphatic sulfinic acid with 1 to 20 carbon atoms, which can be replaced by one or more halogen atoms. In one embodiment, the regulator is a sulfinic acid with a total of 1 to 10 carbon atoms. In one embodiment, the regulator is an aliphatic sulfinic acid with 1 to 10 carbon atoms, which can be replaced by one or more halogen atoms. In one embodiment, the regulator is an aliphatic sulfinic acid with a total of 1 to 8 carbon atoms, which can be replaced by one or more halogen atoms. In one embodiment, the regulator is an aliphatic sulfinic acid with a total of 1 to 6 carbon atoms, which can be replaced by one or more halogen atoms. In one embodiment, the regulator is an aliphatic sulfinic acid with a total of 1 to 4 carbon atoms, which can be replaced by one or more halogen atoms. In one embodiment, the modifier is an aliphatic sulfinic acid having 1 to 3 carbon atoms, which may be substituted with one or more halogen atoms. In one embodiment, the modifier is an aliphatic sulfinic acid having 2 carbon atoms, which may be substituted with one or more halogen atoms.
[0311] In another embodiment, the regulator is an aromatic sulfinic acid having a total of 6 to 20 carbon atoms. In another embodiment, the regulator is an aromatic sulfinic acid having a total of 6 to 10 carbon atoms. In one embodiment, the regulator is an aromatic sulfinic acid having a total of 6 to 8 carbon atoms. The aryl moiety of the aromatic compound can be substituted as defined and exemplified above for the aryl group.
[0312] In one embodiment, the regulator is a sulfenic acid. In one embodiment, the regulator is a sulfenic acid with a total of 1 to 20 carbon atoms. In one embodiment, the regulator is an aliphatic sulfenic acid with 1 to 20 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the regulator is a sulfenic acid with a total of 1 to 10 carbon atoms. In one embodiment, the regulator is an aliphatic sulfenic acid with 1 to 10 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic sulfenic acid with a total of 1 to 8 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic sulfenic acid with a total of 1 to 6 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic sulfenic acid with a total of 1 to 4 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the modifier is an aliphatic sulfenic acid having 1 to 3 carbon atoms, which may be substituted with one or more halogen atoms. In one embodiment, the modifier is an aliphatic sulfenic acid having 2 carbon atoms, which may be substituted with one or more halogen atoms.
[0313] In another embodiment, the modifier is an aromatic sulfenic acid having a total of 6 to 20 carbon atoms. In another embodiment, the modifier is an aromatic sulfenic acid having a total of 6 to 10 carbon atoms. In one embodiment, the modifier is an aromatic sulfenic acid having a total of 6 to 8 carbon atoms. The aryl portion of the aromatic compound can be substituted as defined and exemplified above for the aryl group.
[0314] In one embodiment, the regulator is a phosphonic acid. In one embodiment, the regulator is a phosphonic acid with a total of 1 to 20 carbon atoms. In one embodiment, the regulator is an aliphatic phosphonic acid with 1 to 20 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is a phosphonic acid with a total of 1 to 10 carbon atoms. In one embodiment, the regulator is an aliphatic phosphonic acid with 1 to 10 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphonic acid with a total of 1 to 8 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphonic acid with a total of 1 to 6 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphonic acid with a total of 1 to 4 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphonic acid with 1 to 3 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphonic acid having 2 carbon atoms, which may be substituted by one or more halogen atoms.
[0315] In another embodiment, the regulator is an aromatic phosphonic acid having a total of 6 to 20 carbon atoms. In another embodiment, the regulator is an aromatic phosphonic acid having a total of 6 to 10 carbon atoms. In one embodiment, the regulator is an aromatic phosphonic acid having a total of 6 to 8 carbon atoms.
[0316] In one embodiment, the regulator is phosphoric acid. In one embodiment, the regulator is phosphoric acid with a total of 1 to 20 carbon atoms. In one embodiment, the regulator is an aliphatic phosphoric acid with 1 to 20 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the regulator is a phosphoric acid with a total of 1 to 10 carbon atoms. In one embodiment, the regulator is an aliphatic phosphoric acid with 1 to 10 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphoric acid with a total of 1 to 8 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphoric acid with a total of 1 to 6 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphoric acid with a total of 1 to 4 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphoric acid with 1 to 3 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the modifier is an aliphatic phosphoric acid having 2 carbon atoms, which may be substituted with one or more halogen atoms.
[0317] In another embodiment, the modifier is an aromatic phosphoric acid having a total of 6 to 20 carbon atoms. In another embodiment, the modifier is an aromatic phosphoric acid having a total of 6 to 10 carbon atoms. In one embodiment, the modifier is an aromatic phosphoric acid having a total of 6 to 8 carbon atoms. The aryl portion of the aromatic compound can be substituted as defined and exemplified above for the aryl group.
[0318] In one embodiment, the regulator is a phosphinic acid. In one embodiment, the regulator is a phosphinic acid with a total of 1 to 20 carbon atoms. In one embodiment, the regulator is an aliphatic phosphinic acid with 1 to 20 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is a phosphinic acid with a total of 1 to 10 carbon atoms. In one embodiment, the regulator is an aliphatic phosphinic acid with 1 to 10 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphinic acid with a total of 1 to 8 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphinic acid with a total of 1 to 6 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphinic acid with a total of 1 to 4 carbon atoms, which can be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphinic acid having 1 to 3 carbon atoms, which may be substituted by one or more halogen atoms. In one embodiment, the regulator is an aliphatic phosphinic acid having 2 carbon atoms, which may be substituted by one or more halogen atoms.
[0319] In another embodiment, the regulator is an aromatic phosphinic acid with a total of 6 to 20 carbon atoms. In another embodiment, the regulator is an aromatic phosphinic acid with a total of 6 to 10 carbon atoms. In one embodiment, the regulator is an aromatic phosphinic acid with a total of 6 to 8 carbon atoms. The aryl moiety of the aromatic compound can be substituted as defined and exemplified above with respect to the aryl group.
[0320] In one embodiment, the regulator is an alcohol. In one embodiment, the regulator is an aliphatic alcohol having a total of 1 to 20 carbon atoms. In one embodiment, the regulator is an aliphatic alcohol having a total of 1 to 10 carbon atoms. In one embodiment, the regulator is an aliphatic alcohol having a total of 1 to 8 carbon atoms. In one embodiment, the regulator is an aliphatic alcohol having a total of 1 to 6 carbon atoms. In one embodiment, the regulator is an aliphatic alcohol having a total of 1 to 4 carbon atoms. In one embodiment, the regulator is an aliphatic alcohol having a total of 1 to 3 carbon atoms. In one embodiment, the regulator is an aliphatic alcohol having a total of 2 carbon atoms.
[0321] In another embodiment, the regulator is an aromatic alcohol having a total of 6 to 20 carbon atoms. In another embodiment, the regulator is an aromatic alcohol having a total of 6 to 10 carbon atoms. In one embodiment, the regulator is an aromatic alcohol having a total of 6 to 8 carbon atoms.
[0322] In one embodiment, the regulator is an amine. In one embodiment, the regulator is an aliphatic amine having a total of 1 to 20 carbon atoms. In one embodiment, the regulator is an aliphatic amine having a total of 1 to 10 carbon atoms. In one embodiment, the regulator is an aliphatic amine having a total of 1 to 8 carbon atoms. In one embodiment, the regulator is an aliphatic amine having a total of 1 to 6 carbon atoms. In one embodiment, the regulator is an aliphatic amine having a total of 1 to 4 carbon atoms. In one embodiment, the regulator is an aliphatic amine having a total of 1 to 3 carbon atoms. In one embodiment, the regulator is an aliphatic amine having a total of 2 carbon atoms.
[0323] In another embodiment, the regulator is an aromatic amine having a total of 6 to 20 carbon atoms. In another embodiment, the regulator is an aromatic amine having a total of 6 to 10 carbon atoms. In one embodiment, the regulator is an aromatic amine having a total of 6 to 8 carbon atoms.
[0324] In one embodiment, the modifier is selected from the group consisting of trifluoroacetic acid, trichloroacetic acid, acetic acid, and benzoic acid. In one embodiment, the modifier is trifluoroacetic acid. In one embodiment, the modifier is trichloroacetic acid. In one embodiment, the modifier is acetic acid. In one embodiment, the modifier is benzoic acid.
[0325] In one embodiment, the stoichiometric ratio of modulator to source of linker group is between 50: 1 and 1 :5. In one embodiment, the stoichiometric ratio of modulator to source of linker group is between 20: 1 and 1 :2.
[0326] In one embodiment, the stoichiometric ratio of the modulator to the source of linker groups is between 15: 1 and 5: 1. In one embodiment, the stoichiometric ratio of the modulator to the source of linker groups is between 12: 1 and 8: 1. In one embodiment, the stoichiometric ratio of the modulator to the source of linker groups is between 11: 1 and 9: 1. In one embodiment, the stoichiometric ratio of the modulator to the source of linker groups is 10: 1.
[0327] In one embodiment, the stoichiometric ratio of the modulator to the source of linker groups is between 2:1 and 1:2. In one embodiment, the stoichiometric ratio of the modulator to the source of linker groups is between 1.5:1 and 1:1.5. In one embodiment, the stoichiometric ratio of the modulator to the source of linker groups is between 1.2:1 and 1:1.2. In one embodiment, the stoichiometric ratio of the modulator to the source of linker groups is 1:1.
[0328] In one embodiment, the linker group source is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modulator to benzene-1,3,5-tricarboxylic acid is between 15:1 and 5:1. In one embodiment, the linker group source is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modulator to benzene-1,3,5-tricarboxylic acid is between 12:1 and 8:1. In one embodiment, the linker group source is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modulator to benzene-1,3,5-tricarboxylic acid is between 11:1 and 9:1. In one embodiment, the linker group source is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modulator to benzene-1,3,5-tricarboxylic acid is 10:1.
[0329] In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modifier to benzene-1,3,5-tricarboxylic acid is between 2:1 and 1:2. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modifier to benzene-1,3,5-tricarboxylic acid is between 1.5:1 and 1:1.5. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modifier to benzene-1,3,5-tricarboxylic acid is between 1.2:1 and 1:1.2. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modifier to benzene-1,3,5-tricarboxylic acid is 1:1.
[0330] In one embodiment, the linker group source is benzene-1,3,5-tricarboxylic acid, the modulator is benzoic acid, and the stoichiometric ratio of benzoic acid to benzene-1,3,5-tricarboxylic acid is between 15:1 and 5:1. In one embodiment, the linker group source is benzene-1,3,5-tricarboxylic acid and the modulator is benzoic acid, and the stoichiometric ratio of benzoic acid to benzene-1,3,5-tricarboxylic acid is between 12:1 and 8:1. In one embodiment, the linker group source is benzene-1,3,5-tricarboxylic acid, the modulator is benzoic acid, and the stoichiometric ratio of benzoic acid to benzene-1,3,5-tricarboxylic acid is between 11:1 and 9:1. In one embodiment, the linker group source is benzene-1,3,5-tricarboxylic acid, the modulator is benzoic acid, and the stoichiometric ratio of benzoic acid to benzene-1,3,5-tricarboxylic acid is 10:1.
[0331] In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trichloroacetic acid, and the stoichiometric ratio of trichloroacetic acid to benzene-1,3,5-tricarboxylic acid is between 15:1 and 5:1. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trichloroacetic acid, and the stoichiometric ratio of trichloroacetic acid to benzene-1,3,5-tricarboxylic acid is between 12:1 and 8:1. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trichloroacetic acid, and the stoichiometric ratio of trichloroacetic acid to benzene-1,3,5-tricarboxylic acid is between 11:1 and 9:1. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trichloroacetic acid, and the stoichiometric ratio of trichloroacetic acid to benzene-1,3,5-tricarboxylic acid is 10:1.
[0332] In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modifier to benzene-1,3,5-tricarboxylic acid is between 2:1 and 1:2. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modifier to benzene-1,3,5-tricarboxylic acid is between 1.5:1 and 1:1.5. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modifier to benzene-1,3,5-tricarboxylic acid is between 1.2:1 and 1:1.2. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, and the stoichiometric ratio of the modifier to benzene-1,3,5-tricarboxylic acid is 1:1.
[0333] In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trifluoroacetic acid, and the stoichiometric ratio of trifluoroacetic acid to benzene-1,3,5-tricarboxylic acid is between 2:1 and 1:2. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trifluoroacetic acid, and the stoichiometric ratio of trifluoroacetic acid to benzene-1,3,5-tricarboxylic acid is between 1.5:1 and 1:1.5. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trifluoroacetic acid, and the stoichiometric ratio of trifluoroacetic acid to benzene-1,3,5-tricarboxylic acid is between 1.2:1 and 1:1.2. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trifluoroacetic acid, and the stoichiometric ratio of trifluoroacetic acid to benzene-1,3,5-tricarboxylic acid is 1:1.
[0334] In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trichloroacetic acid, and the stoichiometric ratio of trichloroacetic acid to benzene-1,3,5-tricarboxylic acid is between 2:1 and 1:2. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trichloroacetic acid, and the stoichiometric ratio of trichloroacetic acid to benzene-1,3,5-tricarboxylic acid is between 1.5:1 and 1:1.5. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trichloroacetic acid, and the stoichiometric ratio of trichloroacetic acid to benzene-1,3,5-tricarboxylic acid is between 1.2:1 and 1:1.2. In one embodiment, the source of the linker group is benzene-1,3,5-tricarboxylic acid, the modifier is trichloroacetic acid, and the stoichiometric ratio of trichloroacetic acid to benzene-1,3,5-tricarboxylic acid is 1:1.
[0335] In one embodiment, the stoichiometric ratio of the metal ion source to the modifier is between 1:0.1 and 1:500. In one embodiment, the stoichiometric ratio of the metal ion source to the modifier is between 1:0.2 and 1:200.
[0336] In one embodiment, the method comprises the following sequential steps (a) and (b):
[0337] (a) mixing a metal ion source with a conditioning agent; and
[0338] (b) adding a linker to the mixture formed in step (a).
[0339] In one embodiment, step (a) is performed with stirring. In one embodiment, step (b) is performed with stirring.
[0340] In one embodiment, the synthesis reaction is carried out at an elevated temperature, typically by heating the mixture formed in step (b). Typically, the reaction is carried out at a temperature between 50°C and 250°C. Preferably, the reaction is carried out at a temperature between 100°C and 200°C. More preferably, the reaction is carried out at a temperature between 130°C and 170°C.
[0341] In one embodiment, the reaction time is from 12 hours to 120 hours. In one embodiment, the reaction time is from 24 hours to 96 hours.
[0342] In one embodiment, the method also includes removing the conditioning agent from the composition of the present invention after the composition is synthesized, typically by washing. Without wishing to be bound by theory, it is believed that removing the conditioning agent by washing leaves a composition with multiple hydroxyl groups on the A site of the composition surface. Washing can be carried out using any liquid capable of removing the conditioning agent. Typical materials used include water, alcohol (typically alcohol with 1 to 4 carbon atoms) and mixtures thereof. A particularly preferred example is a mixture of ethanol and water.
[0343] In one embodiment, a certain amount of the modifier remains in the composition after the composition is synthesized. In one embodiment, up to 10% of the modifier remains in the composition after the composition is synthesized. In one embodiment, up to 5% of the modifier remains in the composition after the composition is synthesized. In one embodiment, up to 3% of the modifier remains in the composition after the composition is synthesized. In one embodiment, up to 2% of the modifier remains in the composition after the composition is synthesized. In one embodiment, up to 1% of the modifier remains in the composition after the composition is synthesized. In one embodiment, up to 0.5% of the modifier remains in the composition after the composition is synthesized. In one embodiment, up to 0.3% of the modifier remains in the composition after the composition is synthesized. In one embodiment, up to 0.2% of the modifier remains in the composition after the composition is synthesized. In one embodiment, up to 0.1% of the modifier remains in the composition after the composition is synthesized. These percentages are calculated by weight based on the total weight of the composition.
[0344] In one embodiment, the method is carried out in a solvent. Typical examples of suitable solvents include polar aprotic solvents, examples of which include N,N-dimethylformamide and dimethyl sulfoxide. The polar aprotic solvent may be present in a mixture with water. In one embodiment, the solvent is N,N-dimethylformamide.
[0345] In one embodiment, the stoichiometric ratio of metal ion source to solvent is between 1:10 and 1:200.
[0346] In one embodiment, after the metal ion source and the linker source react, the reaction mixture is cooled to a temperature of less than 10°C, typically between -10°C and 10°C. This step is particularly preferred because the rapid cooling of the composition after the reaction results in a composition with particularly favorable surface properties. Typically, the cooling rate is from 2°C per minute to 20°C per minute. In one embodiment, the cooling rate is from 5°C per minute to 15°C per minute. In one embodiment, the cooling rate is from 8°C per minute to 12°C per minute.
[0347] In one embodiment, the method further comprises removing water so as to cause site B to become Lewis acidic.
[0348] Application of the composition
[0349] Aggregation Methods
[0350] In a further aspect of the invention there is provided the use of a composition of the invention as a catalyst, particularly but not exclusively as a catalyst for catalysing polymerisation reactions.
[0351] In one aspect, a method of forming a polymer is provided, the method comprising polymerizing a monomer in the presence of a composition of the present invention.
[0352] The catalysts can generally be used to catalyze polymerization reactions which are well known to those skilled in the art. In these polymerization reactions, the monomers can be identical (homopolymerization) or different (copolymerization).
[0353] The polymer so formed is typically an organic polymer. A large number of organic polymers are known in the art. Examples of specific classes of organic polymers include polyolefins, polyesters, polycarbonates, polyamides, polyimides, polyethersulfones and mixtures or derivatives thereof.
[0354] In one embodiment, the polymerization is a chain growth reaction or an addition polymerization reaction. Examples of such polymerization reactions include polymerization and copolymerization of ethylenically unsaturated monomers (i.e., compounds having one or more C=C bonds). In one embodiment, the ethylenically unsaturated monomer may be an olefin: in other words, an unsubstituted unsaturated hydrocarbon (such as ethylene, propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, or styrene). In another embodiment, the ethylenically unsaturated monomer is substituted with one or more halogen atoms (such as vinyl chloride, vinylidene fluoride, or tetrafluoroethylene). Examples of polymers produced from such ethylenically unsaturated monomers include, but are not limited to: polyethylene; polypropylene; poly(1-butene); poly(1-pentene); poly(1-hexene); poly(methylpentene); polystyrene; poly(vinylidene fluoride); poly(tetrafluoroethylene) Poly(methyl methacrylate); and mixtures thereof.
[0355] In one embodiment, the polymerization is a step-growth reaction or a condensation polymerization reaction. Examples of such polymerization reactions include the polymerization of polyols and polycarboxylic acids to produce polyesters, and the polymerization of polyamines and polycarboxylic acids to produce polyamides.
[0356] In one embodiment, there is provided a use of the composition of the present invention as a catalyst to catalyze a reaction involving CO 2 reaction, which results in CO 2 is incorporated into the structure of the resulting molecule.
[0357] In one embodiment, CO 2 The molecule with which it reacts comprises a ring structure, so that the reaction causes the ring to open so as to enable the CO 2 incorporated into the molecule.
[0358] In one embodiment, CO 2 The molecule that reacts with it is a monomer, making CO 2 The resulting product into which is incorporated is a polymer. In this specification, such molecules are generally designated as Y. In one embodiment, the polymer formed is a copolymer or terpolymer, at least one repeating unit of the polymer formed comprises CO 2 part and at least one repeating unit lacks CO 2 In one embodiment, the polymer formed is a polycarbonate-polyether copolymer.
[0359] In one embodiment, CO 2 The molecule Y that reacts with it is a monomer, and the reaction promotes polymerization, making CO 2 The resulting product incorporated therein is a polymer.
[0360] In one embodiment, the molecule Y is selected from an epoxide, a lactone or an anhydride.
[0361] In one embodiment, molecule Y is an alkylene oxide, cycloalkylene oxide or an alkylene oxide substituted by an aryl group. In one embodiment, molecule Y is an alkylene oxide, cycloalkylene oxide or an alkylene oxide substituted by an aryl group with a total of 2 to 30 carbon atoms. In one embodiment, molecule Y is an alkylene oxide, cycloalkylene oxide or an alkylene oxide substituted by an aryl group with a total of 2 to 20 carbon atoms. In one embodiment, molecule Y is an alkylene oxide, cycloalkylene oxide or an alkylene oxide substituted by an aryl group with a total of 2 to 10 carbon atoms. In one embodiment, molecule Y is an alkylene oxide with 2 to 6 carbon atoms. In one embodiment, molecule Y is an alkylene oxide with 2 to 4 carbon atoms. In one embodiment, molecule Y is propylene oxide. In one embodiment, molecule Y is ethylene oxide.
[0362] Thus, in a further aspect of the invention, there is provided a method of forming a polymer, wherein CO 2 is incorporated into the structure of the polymer, the method comprising reacting the following in the presence of the composition:
[0363] (a) a molecule Y which is a monomer capable of polymerizing to form a polymer, wherein CO 2 is incorporated into the structure of the polymer; and
[0364] (b)CO 2 ;
[0365] The composition includes a bulk material; and
[0366] at least one surface;
[0367] The bulk material includes ions of metal M bonded to each other via linker groups;
[0368] The surface comprises ions of metal M' bonded to each other via linker groups;
[0369] Metal M and metal M' are the same or different;
[0370] The surface comprises at least one first site A and at least one second different site B;
[0371] Site A has a hydroxyl group bonded thereto, said site A optionally being capable of bonding to a CO 2 interaction;
[0372] Site B is capable of binding CO 2 The molecule makes the bound CO 2 The molecule can react with the monomer molecule Y Lewis acid site;
[0373] The distance d between site A and site B is such that the molecule Y and the bound CO 2 can react together on the surface to form a polymer.
[0374] In one embodiment, the process is carried out at a temperature between 0°C and 150°C.
[0375] In one embodiment, the process is carried out at a temperature between 20°C and 100°C. In one embodiment, the process is carried out at a temperature between 40°C and 80°C.
[0376] In one embodiment, the process is carried out at a temperature between 45° C. and 65° C. This is a lower temperature than is possible in prior art processes using zinc glutarate as catalyst and has the particular advantage of energy and cost savings.
[0377] In one embodiment, the process is carried out at a total pressure between 0.1 MPa and 50 MPa. In one embodiment, the process is carried out at a total pressure between 0.3 MPa and 30 MPa.
[0378] In one embodiment, the process is carried out at a total pressure of between 0.5 MPa and 10 MPa. This is a lower pressure than is possible in prior art processes using zinc glutarate as a catalyst, and has the advantage of additional energy and cost savings.
[0379] In one embodiment, the process is carried out for a period of time lasting between 30 seconds and 1 hour. This is a shorter time than is possible in prior art processes using zinc glutarate as a catalyst, and has the advantage of additional energy and cost savings.
[0380] Including CO 2 Methods for the formation of incorporated cyclic carbonates
[0381] In one embodiment, CO 2 Reacts with molecules to make CO 2 In the present specification, such molecules are generally designated as Y'.
[0382] In one embodiment, the molecule Y' is an epoxide. In this embodiment, the molecule formed is a cyclic carbonate.
[0383] In one embodiment, molecule Y' is an alkylene oxide, an epoxycycloalkane, or an alkylene oxide substituted by an aryl group. In one embodiment, molecule Y' is an alkylene oxide, an epoxycycloalkane, or an alkylene oxide substituted by an aryl group having a total of 2 to 30 carbon atoms. In one embodiment, molecule Y' is an alkylene oxide, an epoxycycloalkane, or an alkylene oxide substituted by an aryl group having a total of 2 to 20 carbon atoms. In one embodiment, molecule Y' is an alkylene oxide, an epoxycycloalkane, or an alkylene oxide substituted by an aryl group having a total of 2 to 10 carbon atoms. In one embodiment, molecule Y' is an alkylene oxide with 2 to 6 carbon atoms. In one embodiment, molecule Y' is an alkylene oxide with 2 to 4 carbon atoms. In one embodiment, molecule Y' is propylene oxide. In one embodiment, molecule Y' is ethylene oxide.
[0384] Thus, in another aspect, the present invention provides a method for forming a cyclic carbonate, wherein CO 2 is incorporated into the structure of a cyclic carbonate, the method comprising reacting the molecule Y' with CO in the presence of a composition 2 Reaction, the composition comprising:
[0385] bulk material; and
[0386] at least one surface;
[0387] The bulk material includes ions of metal M bonded to each other via linker groups;
[0388] The surface comprises ions of metal M' bonded to each other via linker groups;
[0389] Metal M and metal M' are the same or different;
[0390] The surface comprises at least one first site A and at least one second different site B;
[0391] Site A has a hydroxyl group -X bonded thereto;
[0392] Site B is capable of binding CO 2 The molecule makes the bound CO 2 Lewis acid sites at which the molecule can react with molecule Y';
[0393] Site B has a Lewis base bound to it;
[0394] The distance d" between site A and site B is such that the molecule Y and the adsorbed CO 2 can react together on the surface to form a cyclic carbonate.
[0395] When the composition of the present invention includes a B-site to which a Lewis base is bound (e.g. Figure 4), the reaction catalyzed by the composition typically produces a cyclic carbonate.
[0396] The polymer obtained by this method
[0397] In a further aspect, the invention also provides a polymer obtainable or obtained according to the method of the invention.The polymer may comprise one type of monomer (homopolymer) or two or more types of monomers (copolymer).
[0398] The polymer so formed is typically an organic polymer. A large number of organic polymers are known in the art. Examples of specific classes of organic polymers include polyolefins, polyesters, polycarbonates, polyamides, polyimides, polyethersulfones and mixtures or derivatives thereof.
[0399] Examples of polymers produced from ethylenically unsaturated monomers include, but are not limited to: polyethylene; polypropylene; poly(1-butene); poly(1-pentene); poly(1-hexene); poly(methylpentene); polystyrene; poly(vinylidene fluoride); poly(tetrafluoroethylene) Poly(methyl methacrylate); and mixtures thereof.
[0400] In one embodiment, the polymer formed is a copolymer or terpolymer, and at least one repeating unit of the polymer formed comprises CO 2 part and at least one repeating unit lacks CO 2 part.
[0401] In one embodiment, when monomer Y is an epoxide, the polymer formed is a polycarbonate-polyether copolymer. Scheme 1 generally illustrates the ring opening copolymerization (ROCOP) between propylene oxide (PO) to produce poly(propylene) carbonate (PPC), poly(propylene) ether (PPE) and cyclic propylene carbonate (CPC).
[0402]
[0403] Depending on the structure of the catalyst composition, the resulting polymer may have varying ratios of carbonate repeating units and ether repeating units.
[0404] When the composition of the invention includes a linker unit lacking a non-coordinating group R' as part of the linker (e.g. Figure 1 ), reactions catalyzed by the composition typically produce a low proportion of cyclic carbonate by-products and polycarbonate-polyether copolymers having a greater proportion of carbonate units than ether units (in Scheme 1, x is much greater than y).
[0405] When the composition of the present invention includes a linker unit having a non-coordinating group R' as part of the linker (e.g. Figure 2 The reaction catalyzed by the composition generally produces a polycarbonate-polyether copolymer and a low proportion of cyclic carbonate byproducts. However, compared with compositions lacking non-coordinating groups R' as part of the linker, the compositions of the present invention include linker units having non-coordinating groups R' as part of the linker, which generally produce polycarbonate-polyether copolymers having a reduced proportion of carbonate units compared to ether units. The proportion of carbonate units varies depending on the nature of the non-coordinating groups R' and the proportion of linker units comprising the groups.
[0406] When the composition of the present invention comprises Figure 3 When the linker units are generally shown in Scheme 1, the reaction catalyzed by the composition generally produces a low proportion of cyclic carbonate by-products and such polycarbonate-polyether copolymers having a much lower proportion of carbonate units than ether units (in Scheme 1, x is much less than y).
[0407] In one embodiment, the polymer has greater than 70%, greater than 80%, greater than 85%, greater than 90%, greater than 97%, greater than 98%, or greater than 99% carbonate linkage incorporation.
[0408] In one embodiment, the polymer has a number average molecular weight (M) of less than 10 kDa. n In one embodiment, the polymer has a number average molecular weight (M) between 2 kDa and 9 kDa. n ). As indicated above, the use of the composition according to the present invention allows the production of such a polymer, which has a lower molecular weight than similar compositions of the prior art. The number average molecular weight can be measured by size exclusion chromatography. As known to those skilled in the art, size exclusion chromatography is one of the separation modes of high pressure liquid chromatography (HPLC). Typically, the column used is filled with a material comprising many pores. When dissolved molecules of various sizes flow into the column, smaller dissolved molecules flow more slowly through the column because they penetrate deeply into the pores, while large dissolved molecules flow quickly through the column because they do not enter the pores. Therefore, larger molecules are eluted from the column earlier, and smaller molecules are eluted from the column later, which effectively classifies molecules by size. This is the separation principle of size exclusion chromatography. An example of such a method is described in Shimadzu Gel Permeation Chromatography System-Application Data Handbook-(C190-0032, page 81).
[0409] General method 1
[0410] According to the present invention, the two different metal ions M in a molar ratio of 4:1 are included. 1 and M 2 The heterogeneous catalyst platform was prepared by stirring at room temperature in a 0.108 M solution of the modifier in DMF (4 mL). 1 (0.688mmol) and M 2 (0.172 mmol) of the salt was synthesized. After homogenization, the linker (0.430 mmol) in DMF was added and the solution was further stirred. The resulting solution was sealed in a 23 mL The interior of the autoclave was lined and heated to 150° C. for 48 hours, after which the autoclave was removed from the oven and rapidly cooled (at a rate of about 10° C. per minute) to less than 10° C. The synthesized heterogeneous catalyst platform was collected by filtration and washed with deionized water and then with ethanol. Example
[0411] Example 1 - Synthesis of the Surface Engineered Compositions of the Invention
[0412] Scandium nitrate hydrate (0.240 g) was dissolved in DMF (4 mL) and stirred vigorously at room temperature until dissolved. Benzoic acid (0.550 g) was added to the solution. The solution was stirred again until homogeneous. Benzene-1,3,5-tricarboxylic acid (0.091 g) and DMF (4 mL) were added to the solution. The solution was stirred until homogeneous. The resulting solution was sealed in a 23 mL The interior of the lined autoclave was heated in an oven at 150° C. for 48 hours, after which the autoclave was removed and rapidly cooled (at a rate of about 10° C. per minute) to less than 10° C. The resultant composition was filtered and washed with ethanol and water.
[0413] The composition has the general formula [Sc 3 O(OH)(BTC) 2 ], as demonstrated by the following technique.
[0414] A range of physicochemical techniques have been used to analyse the composition.
[0415] PDF( Figure 5 ) was used to confirm that the scaffold structure was correctly crystallized. 45 Sc MAS NMR( Figure 6 ) confirmed the existence of A-site and B-site. 2 Physical adsorption ( Figure 7 ) confirmed that the scaffold was porous and provided surface area analysis. Electron microscopy (SEM and TEM) techniques confirmed the particle size distribution ( Figure 8 and Fig. 9 ).
[0416] To evaluate the catalytic efficiency, propylene oxide (5.000 g) was placed into a 100 mL PEEK liner. The surface engineered catalyst (0.040 g) was added to the liner. The liner was placed in the reactor base of a 100 mL Parr batch reactor unit and sealed to the head unit. The reactor was operated with CO 2 Purge, then fill to 2MPa CO 2 The reactor was heated to 65°C and the reaction time started after reaching this temperature. After 4 hours, the reactor was quickly cooled to 0°C on ice. The product mixture was heated to 65°C and the reaction time started after reaching this temperature. 3 In 1 The polymer products were analyzed by size exclusion chromatography (SEC).
[0417] PDF data were collected on a Rigaku R-Axis 3-circle Spider goniometer equipped with a curved Fujifilm image plate mounted on a graphite monochrome sealed tube silver operated at 1.2 kW (40 kV, 30 mA). The sample was loaded into a borosilicate capillary of 1 mm diameter and 0.01 mm wall thickness. The capillary was placed at a distance of 127.4 mm from the detector. The exposure time per oscillation ω degree was 84 s, and an oscillation ω of 84° was used, giving a total collection time of 117.6 minutes. The collected 2D powder maps were integrated into a 1D total scattering map using Rigaku 2DP software and converted to a pair distribution function using GudrunX.
[0418] Magic angle spinning nuclear magnetic resonance (MAS-NMR) measurements were collected at the UK 850 MHz solid-state NMR facility at the University of Warwick on a wide-bore 20.0 T Bruker AVANCE III spectrometer with a Neo console using a 4.0 mm HXY probe in double resonance mode. 2 The samples were loaded into a 4.0 mm zirconium oxide Bruker NMR rotor with a vespel turbine under atmosphere. 45 Sc spectrum ( 45 Sc Larmor frequency = 206.51MHz) Reference D 2 1mmol ScCl in O 3 , using 192 scans and a pulse delay (d1) of 1 s. 2 For driving, carrying and purging. The measurements were carried out at a rotation rate of 13.5 kHz.
[0419] N2 Adsorption measurements were performed at liquid nitrogen temperature using a Micromeritics ASAP 2020. Samples were degassed in vacuum at 150° C. Surface area measurements were determined using the Brunauer, Emmett and Teller (BET) model (originally described in J. Am. Chem. Soc. 1938, 60(2): 309-319).
[0420] Scanning electron microscopy (SEM) images were obtained using a FEI Quanta 250 FEG scanning electron microscope, where the samples were mounted on carbon tape and sputter coated with a 7 mm layer of platinum.
[0421] Transmission electron microscopy (TEM) images were acquired using a Hitachi HT7700 equipped with a LaB6 filament and operated at an accelerating voltage of 100 kV. Samples were sonicated in ethanol, pipetted onto carbon-coated 200 mesh copper TEM grids, and allowed to dry in air before imaging.
[0422] Solution NMR for polymer analysis was performed on a Bruker AV400 FT-NMR spectrometer in CDCl 3 Chemical shifts were referenced to tetramethylsilane (TMS).
[0423] Size Exclusion Chromatography (SEC / GPC) analysis was performed on a Shimadzu LC-20AD instrument equipped with a refractive index (RI) detector and two PSSSDV 5 μm linear M columns. HPLC grade THF was used as eluent at 30°C with 1.0 mL / min. The sample was passed through a 0.2 μm PTFE filter before analysis. Monodisperse polystyrene standards were used for calibration. Narrow MW polystyrene standards were used to calibrate the instrument. The method is described in the Shimadzu Gel Permeation Chromatography System - Application Data Handbook - (C190-0032, page 81).
[0424] Example 2 - Comparison of the catalytic activity of the surface engineered compositions of the present invention with known catalysts
[0425] The surface engineered composition according to the present invention, as prepared in Example 1, is effective against propylene oxide and CO 2 The catalytic activity of the copolymerization of 2 The catalysts were evaluated by the amount of catalytic activity (key indicator inserted) and their catalytic efficiency (turnover frequency, TOF). The complete catalytic data are in Table 1. Under the conditions stated in the table, the catalytic performance was compared with a DMC catalyst and a zinc glutarate catalyst as described in the literature.
[0426] The reaction is carried out without solvent, using only pure epoxide, catalyst and CO 2 Unless otherwise stated, all reactions shown were performed without thermal treatment. This is in contrast to the lengthy activation procedures performed with current heterogeneous catalyst systems, which require lengthy dehydration under vacuum (ZnGAs) or exothermic preactivation with epoxide monomers (DMCs).
[0427]
[0428]
[0429] Table 1: Reaction conditions and activity data for heterogeneous copolymerization catalysts.
[0430] In Table 1, the references are as follows (1) M. Ree et al., J. Polym. Sci. Part Polym.Chem., 1999, 37, 1863-1876; (2) S.Klaus et al., J.Am.Chem.Soc., 2011, 133, 13151-13161; (3) R.-R.Ang et al., Chem.Eng.J., 2017, 327, 120-127; (4) J.-S.Kim et al., J.Catal., 2003, 218, 209-219; (5) I.Kim et al., Macromol.Symp., 2005, 224, 181-192; (6) I.Kim et al., Catal.Today, 2006, 111, 292-296; (7) S.Chen et al., J.Polym.Sci.Part. Polym.Chem., 2004, 42, 5284-5291; (8) N.Almora-Barrios et al., ChemCatChem, 2015, 7, 928-935; (9) Q.Meng et al., J.CO2 Util., 2016, 16, 86-96.
[0431] The selectivity of the composition of the present invention for producing polycarbonate-polyether copolymers (compared to cyclic carbonates) is Fig.10 As can be seen, the selectivity is comparable to that of a Robson type homogeneous catalyst and is improved compared to a zinc glutarate heterogeneous catalyst.
[0432] exist Fig.11The graph in the middle shows the turnover frequency of the composition of the present invention in this polymerization reaction, which is defined as: (mass of polymer) / (mass of active metal in catalyst*reaction time). As can be seen, the turnover frequency of the composition in this reaction is improved by about 50% compared to the Robson type homogeneous catalyst, and is about 8 times the turnover frequency of the zinc glutarate heterogeneous catalyst.
[0433] Table 1 and Fig.10 and Fig.11 The data show that the synthesized ZnGA catalyst and the reported catalysts in the literature produce catalysts with high carbonate bonds and consistent dispersion. The surface engineered compositions according to the present invention show excellent catalytic activity compared to catalysts of polymers. These results were obtained using lower temperature and pressure conditions than those reported in the literature. Under these conditions, the ZnGA catalyst did not provide significant conversion to cyclic carbonate materials or polycarbonate materials. In order to induce reactivity, the ZnGA system required an increase in pressure to 4 MPa and an increase in temperature to 80°C. Under the selected conditions, the surface engineered catalyst was able to achieve a reaction time of more than 1400 h. -1 TOF frequency while providing equivalent carbonate bonds in the polymer backbone.
[0434] Under the same conditions in which cyclic carbonate was used as a starting material, no polymerization was observed, confirming that the cyclic carbonate was formed by competitive parallel reactions and was not an intermediate in the polymerization process.
[0435] It is clear from these results that the surface engineered compositions of the present invention allow carbon dioxide and propylene oxide to be uniquely activated in a manner not previously observed in MOF-based catalytic chemistry to provide exceptional catalytic activity and high levels of CO 2 Without wishing to be bound by theory, we propose a copolymerization pathway illustrated in Scheme 2, where the metal M is Sc, the left-hand site is the A-site and the right-hand site is the B-site (identified in box (a)). This is Figure 6 Observed in 45 Sc MAS-NMR spectroscopy support.
[0436]
[0437] Example 3 - Synthetic Method for Producing Compositions of the Invention Having Two Different Metal Ions
[0438] The heterogeneous catalyst platform was synthesized by stirring scandium nitrate (0.688 mmol) and chromium nitrate hexahydrate (0.172 mmol) in a 0.108 M solution of acetic acid in DMF (4 mL) at room temperature. After homogenization, benzene-1,3,5-tricarboxylic acid (BTC, 0.430 mmol) in DMF was added and the solution was further stirred. The resulting solution was sealed in a 23 mL The interior of the autoclave was lined and heated to 150° C. for 48 hours, after which the autoclave was removed from the oven and rapidly cooled (at a rate of about 10° C. per minute) to less than 10° C. The synthesized heterogeneous catalyst platform was collected by filtration and washed with deionized water and then with ethanol.
[0439] Example 4 - Additional compositions of the invention with different modulators
[0440] Many additional surface engineered compositions were prepared using a variety of modulators and different modulator: linker ratios. For comparison, controls were prepared without modulators. Compositions 1 to 4 were prepared as generally described in Example 1. Compositions 5 and 6 were prepared according to General Method 1.
[0441] The compositions, modulators used and the molar ratios of modulator to linker group source are shown below in Table 2. In Table 2, the abbreviations have the following meanings.
[0442] BTC=Benzene-1,3,5-tricarboxylic acid
[0443] TFA = trifluoroacetic acid
[0444] TCA = trichloroacetic acid
[0445] BA = Benzoic acid
[0446]
[0447] Table 2
[0448] The compositions were examined by TEM using the same equipment and methods as used in Example 1. The average crystallite size was measured according to the method described in CA Schneider et al., Nature Methods, 2012, 9(7), 671-675 using ImageJ software (available from imagej.nih.gov).
[0449] The TEM images of compositions 1 to 4 are respectively Figures 12 to 15 The TEM image of the control is shown in Fig.16As can be seen from the TEM images, the crystallite size and particle morphology differ depending on the identity of the modifier and the modifier:linker stoichiometry. In the control composition without modifier, the particles are large agglomerates with no discernible shape and an average crystallite size of about 66 nm. Using TFA as modifier in composition 1, uniform spherical particles of about 300 nm size including 67 nm crystallites can be obtained. Using BA in composition 2, a very large distribution of single crystals can be obtained, which are not agglomerates at all.
[0450] Example 5 - Catalytic Activity of the Composition of Example 4
[0451] The surface engineered composition prepared in Example 4 was used to catalyze the reaction of propylene oxide with CO 2 The catalytic activity in the copolymerization of n ) and the dispersibility of the polymers synthesized therefrom.
[0452] The results are shown in Table 3. Number average molecular weight (M n ) was measured using size exclusion chromatography using the equipment and method described in Example 1. Dispersibility Calculated as the number average molecular weight (M n ) divided by the weight average molecular weight (M w ). n and M w Both were measured using size exclusion chromatography using the same equipment and methods described in Example 1.
[0453]
[0454] Table 3
[0455] By way of comparison, the number average molecular weight (M) of poly(propylene carbonate) polymers formed using the zinc glutaracetate / double metal cyanide composite catalyst described in Meng et al. n ) and dispersibility are shown in Table 4. As is clear from the comparison of the data in Table 3 and Table 4, the composition of the present invention is able to catalyze the reaction of propylene oxide and CO 2 The copolymerization of n ) which is commercially more expensive than polymers having a higher M n The polymer is more useful.
[0456]
[0457] Table 4
[0458] We have demonstrated the first example of a recyclable surface-engineered hybrid catalyst that is able to selectively produce poly(propylene) carbonate from propylene oxide and carbon dioxide under conditions much milder than those currently explored in the literature. The provided polymer backbone contains a very high percentage of carbonate bonds, rendering the catalyst efficient for CO insertion. 2 The ability to capture carbon dioxide - an important step in the development of carbon capture and utilization technology. The surface engineered catalyst according to the present invention is able to provide such excellent catalysis without the use of a co-catalyst, with a nearly four-fold increase in turnover frequency compared to the most widely used commercial catalyst.
[0459] All publications mentioned in the above description are incorporated herein by reference. Without departing from the scope and spirit of the present invention, multiple modifications and variations of the present invention will be apparent to those skilled in the art. Although the present invention has been described in conjunction with specific preferred embodiments, it should be understood that the present invention as claimed should not be overly limited to such specific embodiments. In fact, it is apparent to the technicians of chemistry, materials science or related fields that multiple modifications of the described mode for implementing the present invention are intended to be within the scope of the appended claims.
Claims
1. A composition comprising: body material; as well as at least one surface; The bulk material includes ions of metal M bonded to each other via linker groups; The surface comprises ions of metal M' bonded to each other via linker groups; The metal M and the metal M' are the same or different; The surface comprises at least one first site A and at least one second different site B; The site A has a hydroxyl group bonded thereto, the site A optionally being capable of interacting with CO2; The site B is a Lewis acid site capable of binding a CO2 molecule; The distance d between the site A and the site B enables the monomer molecule Y and the bound CO2 to react together on the surface to form a polymer, wherein the CO2 is incorporated into the structure of the polymer.
2. A composition comprising: body material; as well as at least one surface; The bulk material includes ions of metal M bonded to each other via linker groups; The surface comprises ions of metal M' bonded to each other via linker groups; The metal M and the metal M' are the same or different; The surface comprises at least one first site A and at least one second different site B; The site A has a hydroxyl group bonded thereto, and the site A is capable of interacting with a monomer molecule; The site B is a Lewis acid site, and the site B can interact with a monomer molecule; The distance d between the site A and the site B enables monomer molecules to polymerize on the surface to form a polymer.
3. A composition comprising: body material; as well as at least one surface; The bulk material includes ions of metal M bonded to each other via linker groups; The surface comprises ions of metal M' bonded to each other via linker groups; The metal M and the metal M' are the same or different; The surface comprises at least one first site A and at least one second different site B; The site A has a hydroxyl group bonded thereto, and the site A is capable of interacting with a monomer molecule; The site B is a Lewis acid site, and the site B can interact with a monomer molecule; The composition is obtainable by reacting a source of metal ions M and a source of metal ions M' with a source of linker groups and a source of hydroxyl groups in the presence of a modulator under conditions such that the surface of the composition has a first site A to which the hydroxyl groups are bound and a second site B that is Lewis acidic.
4. The composition according to any one of claims 1 to 3, which is a microcrystalline composition.
5. A microcrystalline composition comprising: body material; as well as at least one surface; The bulk material includes ions of metal M bonded to each other via linker groups; The surface comprises ions of metal M' bonded to each other via linker groups; The metal M and the metal M' are the same or different; The surface comprises at least one first site A and at least one second different site B; The site A has a hydroxyl group bonded thereto, and the site A is capable of interacting with a monomer molecule; The site B is a Lewis acid site, and the site B can interact with a monomer molecule.
6. The composition according to any one of claims 1 to 5, wherein the metal ion M and the metal M' are selected from Sc 3+ Cr 3+ 、Al 3+ and Fe 3+ .
7. The composition according to any one of claims 1 to 5, wherein the linker group has the structure T(R) x (R') y (H) z ,in: T is a multivalent organic moiety; R is a functional group capable of coordinating with metal ion M and metal ion M'; R' is a functional group that cannot coordinate with metal ion M and metal ion M', which functional group is not H; x is 2 to 6; y is 0 to 4; and z is a number sufficient to occupy the remaining valences on T.
8. A method of forming a composition according to any one of claims 1 to 7, comprising reacting a source of metal ions M and a source of metal ions M' with a source of linker groups and a source of hydroxyl groups in the presence of a modifier; and subjecting the composition to conditions such that the surface of the composition has a first site A to which the hydroxyl groups are attached and a second site B that is Lewis acidic.
9. The method of claim 8, wherein the stoichiometric ratio of the modulator to the source of linker groups is between 50:1 and 1:
5.
10. The method of claim 8, wherein the stoichiometric ratio of the modulator to the source of linker groups is between 20:1 and 1:
2.
11. The method according to claim 8, wherein the stoichiometric ratio of the source of metal ions M and the source of metal ions M' to the modifier is between 1:0.1 and 1:
500.
12. The method of claim 8, wherein the modifier is selected from the group consisting of trifluoroacetic acid, trichloroacetic acid, acetic acid, and benzoic acid.
13. The method according to any one of claims 8 to 12, comprising the following sequential steps (a) and (b): (a) mixing the metal ion M source and the metal ion M' source with the conditioning agent; and (b) adding the linker group source to the mixture formed in step (a).
14. The method according to claim 13, wherein the method is carried out in a solvent and the stoichiometric ratio of the source of metal ions M and the source of metal ions M' to the solvent is between 1:10 and 1:
200.
15. The method according to any one of claims 8 to 14, wherein after the reaction of the sources of metal ions M and M' and the source of linker groups, the reaction mixture is cooled to a temperature of less than 10°C.
16. A catalyst obtainable by a process according to any one of claims 8 to 15.
17. Use of the composition according to any one of claims 1 to 7 as a catalyst.
18. The use according to claim 17, wherein the catalyst is used to catalyze a polymerization reaction.
Citation Information
Patent Citations
Process for the preparation of polycarbonates
CA1262597A
Carbon dioxide oxirane copolymers prepared using double metal cyanide complexes
US4500704A
Process for the preparation of polycarbonates from epoxy compound and carbon dioxide
US4826953A
Making poly(alkylene carbonates) of controlled molecular weight
US4943677A
Zinc-containing solid catalyst, process of preparing same and process for preparing polyalkylene carbonate
US4981948A
